Radius functions on Poisson–Delaunay mosaics and related complexes experimentally - Edelsbrunner, Herbert; Nikitenko, Anton; Ölsböck, Katharina; Synak, Peter (Topological Data Analysis)
Discrete Morse theory has recently lead to new developments in the theory of random geometric complexes. This article surveys the methods and results obtained with this new approach, and discusses some of its shortcomings. It uses simulations to illustrate the results and to form conjectures, getting numerical estimates for combinatorial, topological, and geometric properties of weighted and unweighted Delaunay mosaics, their dual Voronoi tessellations, and the Alpha and Wrap complexes contained in the mosaics.

Amplified centrosomes in dendritic cells promote immune cell effector functions - Hauschild, Robert

Filling the antibody pipeline in allergy: PIPE cloning of IgE, IgG1 and IgG4 against the major birch pollen allergen Bet v 1 - Köhler, Verena K.; Crescioli, Silvia; Fazekas-Singer, Judit; Bax, Heather J.; Hofer, Gerhard; Pranger, Christina L.; Hufnagl, Karin; Bianchini, Rodolfo; Flicker, Sabine; Keller, Walter; Karagiannis, Sophia N.; Jensen-Jarolim, Erika (International Journal of Molecular Sciences)
Birch pollen allergy is among the most prevalent pollen allergies in Northern and Central Europe. This IgE-mediated disease can be treated with allergen immunotherapy (AIT), which typically gives rise to IgG antibodies inducing tolerance. Although the main mechanisms of allergen immunotherapy (AIT) are known, questions regarding possible Fc-mediated effects of IgG antibodies remain unanswered. This can mainly be attributed to the unavailability of appropriate tools, i.e., well-characterised recombinant antibodies (rAbs). We hereby aimed at providing human rAbs of several classes for mechanistic studies and as possible candidates for passive immunotherapy. We engineered IgE, IgG1, and IgG4 sharing the same variable region against the major birch pollen allergen Bet v 1 using Polymerase Incomplete Primer Extension (PIPE) cloning. We tested IgE functionality and IgG blocking capabilities using appropriate model cell lines. In vitro studies showed IgE engagement with FcεRI and CD23 and Bet v 1-dependent degranulation. Overall, we hereby present fully functional, human IgE, IgG1, and IgG4 sharing the same variable region against Bet v 1 and showcase possible applications in first mechanistic studies. Furthermore, our IgG antibodies might be useful candidates for passive immunotherapy of birch pollen allergy.

Epinephrine drives human M2a allergic macrophages to a regulatory phenotype reducing mast cell degranulation in vitro - Gotovina, Jelena; Bianchini, Rodolfo; Fazekas-Singer, Judit; Herrmann, Ina; Pellizzari, Giulia; Haidl, Ian D.; Hufnagl, Karin; Karagiannis, Sophia N.; Marshall, Jean S.; Jensen‐Jarolim, Erika (Allergy)

RGtracker - Hauschild, Robert
Automated root growth analysis and tracking of root tips.

GRANDPA: A Byzantine finality gadget - Stewart, Alistair; Kokoris Kogias, Eleftherios (arXiv)
Classic Byzantine fault-tolerant consensus protocols forfeit liveness in the face of asynchrony in order to preserve safety, whereas most deployed blockchain protocols forfeit safety in order to remain live. In this work, we achieve the best of both worlds by proposing a novel abstractions called the finality gadget. A finality gadget allows for transactions to always optimistically commit but informs the clients that these transactions might be unsafe. As a result, a blockchain can execute transactions optimistically and only commit them after they have been sufficiently and provably audited. In this work, we formally model the finality gadget abstraction, prove that it is impossible to solve it deterministically in full asynchrony (even though it is stronger than consensus) and provide a partially synchronous protocol which is currently securing a major blockchain. This way we show that the protocol designer can decouple safety and liveness in order to speed up recovery from failures. We believe that there can be other types of finality gadgets that provide weaker safety (e.g., probabilistic) in order to gain more efficiency and this can depend on the probability that the network is not in synchrony.

Reverse firewalls for actively secure MPCs - Chakraborty, Suvradip; Dziembowski, Stefan; Nielsen, Jesper Buus (Advances in Cryptology – CRYPTO 2020)
Reverse firewalls were introduced at Eurocrypt 2015 by Miro-nov and Stephens-Davidowitz, as a method for protecting cryptographic protocols against attacks on the devices of the honest parties. In a nutshell: a reverse firewall is placed outside of a device and its goal is to “sanitize” the messages sent by it, in such a way that a malicious device cannot leak its secrets to the outside world. It is typically assumed that the cryptographic devices are attacked in a “functionality-preserving way” (i.e. informally speaking, the functionality of the protocol remains unchanged under this attacks). In their paper, Mironov and Stephens-Davidowitz construct a protocol for passively-secure two-party computations with firewalls, leaving extension of this result to stronger models as an open question. In this paper, we address this problem by constructing a protocol for secure computation with firewalls that has two main advantages over the original protocol from Eurocrypt 2015. Firstly, it is a multiparty computation protocol (i.e. it works for an arbitrary number n of the parties, and not just for 2). Secondly, it is secure in much stronger corruption settings, namely in the active corruption model. More precisely: we consider an adversary that can fully corrupt up to 𝑛−1 parties, while the remaining parties are corrupt in a functionality-preserving way. Our core techniques are: malleable commitments and malleable non-interactive zero-knowledge, which in particular allow us to create a novel protocol for multiparty augmented coin-tossing into the well with reverse firewalls (that is based on a protocol of Lindell from Crypto 2001).

Improved discrete Gaussian and subgaussian analysis for lattice cryptography - Genise, Nicholas; Micciancio, Daniele; Peikert, Chris; Walter, Michael (23rd IACR International Conference on the Practice and Theory of Public-Key Cryptography)
Discrete Gaussian distributions over lattices are central to lattice-based cryptography, and to the computational and mathematical aspects of lattices more broadly. The literature contains a wealth of useful theorems about the behavior of discrete Gaussians under convolutions and related operations. Yet despite their structural similarities, most of these theorems are formally incomparable, and their proofs tend to be monolithic and written nearly “from scratch,” making them unnecessarily hard to verify, understand, and extend. In this work we present a modular framework for analyzing linear operations on discrete Gaussian distributions. The framework abstracts away the particulars of Gaussians, and usually reduces proofs to the choice of appropriate linear transformations and elementary linear algebra. To showcase the approach, we establish several general properties of discrete Gaussians, and show how to obtain all prior convolution theorems (along with some new ones) as straightforward corollaries. As another application, we describe a self-reduction for Learning With Errors (LWE) that uses a fixed number of samples to generate an unlimited number of additional ones (having somewhat larger error). The distinguishing features of our reduction are its simple analysis in our framework, and its exclusive use of discrete Gaussians without any loss in parameters relative to a prior mixed discrete-and-continuous approach. As a contribution of independent interest, for subgaussian random matrices we prove a singular value concentration bound with explicitly stated constants, and we give tighter heuristics for specific distributions that are commonly used for generating lattice trapdoors. These bounds yield improvements in the concrete bit-security estimates for trapdoor lattice cryptosystems.

The mitochondrial carrier pathway transports non-canonical substrates with an odd number of transmembrane segments - Rampelt, Heike; Sucec, Iva; Bersch, Beate; Horten, Patrick; Perschil, Inge; Martinou, Jean-Claude; van der Laan, Martin; Wiedemann, Nils; Schanda, Paul; Pfanner, Nikolaus (BMC Biology)
Background: The mitochondrial pyruvate carrier (MPC) plays a central role in energy metabolism by transporting pyruvate across the inner mitochondrial membrane. Its heterodimeric composition and homology to SWEET and semiSWEET transporters set the MPC apart from the canonical mitochondrial carrier family (named MCF or SLC25). The import of the canonical carriers is mediated by the carrier translocase of the inner membrane (TIM22) pathway and is dependent on their structure, which features an even number of transmembrane segments and both termini in the intermembrane space. The import pathway of MPC proteins has not been elucidated. The odd number of transmembrane segments and positioning of the N-terminus in the matrix argues against an import via the TIM22 carrier pathway but favors an import via the flexible presequence pathway. Results: Here, we systematically analyzed the import pathways of Mpc2 and Mpc3 and report that, contrary to an expected import via the flexible presequence pathway, yeast MPC proteins with an odd number of transmembrane segments and matrix-exposed N-terminus are imported by the carrier pathway, using the receptor Tom70, small TIM chaperones, and the TIM22 complex. The TIM9·10 complex chaperones MPC proteins through the mitochondrial intermembrane space using conserved hydrophobic motifs that are also required for the interaction with canonical carrier proteins. Conclusions: The carrier pathway can import paired and non-paired transmembrane helices and translocate N-termini to either side of the mitochondrial inner membrane, revealing an unexpected versatility of the mitochondrial import pathway for non-cleavable inner membrane proteins.
Keywords: Biotechnology; Plant Science; General Biochemistry; Genetics and Molecular Biology; Developmental Biology; Cell Biology; Physiology; Ecology; Evolution; Behavior and Systematics; Structural Biology; General Agricultural and Biological Sciences

Architecture and subunit dynamics of the mitochondrial TIM9·10·12 chaperone - Weinhäupl, Katharina; Wang, Yong; Hessel, Audrey; Brennich, Martha; Lindorff-Larsen, Kresten; Schanda, Paul (bioRxiv)
The mitochondrial Tim chaperones are responsible for the transport of membrane proteins across the inter-membrane space to the inner and outer mitochondrial membranes. TIM9·10, a hexameric 70 kDa protein complex formed by 3 copies of Tim9 and Tim10, guides its clients across the aqueous compartment. The TIM9·10·12 complex is the anchor point at the inner-membrane insertase complex TIM22. The mechanism of client transport by TIM9·10 has been resolved recently, but the structure and subunit composition of the TIM9·10·12 complex remains largely unresolved. Furthermore, the assembly process of the hexameric TIM chaperones from its subunits remained elusive. We investigate the structural and dynamical properties of the Tim subunits, and show that they are highly dynamic. In their non-assembled form, the subunits behave as intrinsically disordered proteins; when the conserved cysteines of the CX 3 C-X n -CX 3 C motifs are formed, short marginally stable α -helices are formed, which are only fully stabilized upon hexamer formation to the mature chaperone. Subunits are in equilibrium between their hexamer-embedded and a free form, with exchange kinetics on a minutes time scale. Joint NMR, small-angle X-ray scattering and MD simulation data allow us to derive a structural model of the TIM9·10·12 assembly, which has a 2:3:1 stoichiometry (Tim9:Tim10:Tim12) with a conserved hydrophobic client-binding groove and flexible N- and C-terminal tentacles.

Structural basis of client specificity in mitochondrial membrane-protein chaperones - Sučec, Iva; Wang, Yong; Dakhlaoui, Ons; Weinhäupl, Katharina; Jores, Tobias; Costa, Doriane; Hessel, Audrey; Brennich, Martha; Rapaport, Doron; Lindorff-Larsen, Kresten; Bersch, Beate; Schanda, Paul (bioRxiv)
Chaperones are essential for assisting protein folding, and for transferring poorly soluble proteins to their functional locations within cells. Hydrophobic interactions drive promiscuous chaperone–client binding, but our understanding of how additional interactions enable client specificity is sparse. Here we decipher what determines binding of two chaperones (TIM8·13, TIM9·10) to different integral membrane proteins, the all-transmembrane mitochondrial carrier Ggc1, and Tim23 which has an additional disordered hydrophilic domain. Combining NMR, SAXS and molecular dynamics simulations, we determine the structures of Tim23/TIM8·13 and Tim23/TIM9·10 complexes. TIM8·13 uses transient salt bridges to interact with the hydrophilic part of its client, but its interactions to the transmembrane part are weaker than in TIM9·10. Consequently, TIM9·10 outcompetes TIM8·13 in binding hydrophobic clients, while TIM8·13 is tuned to few clients with both hydrophilic and hydrophobic parts. Our study exemplifies how chaperones fine-tune the balance of promiscuity vs. specificity.

ARCH-COMP20 Category Report: Continuous and hybrid systems with linear dynamics - Althoff, Matthias; Bak, Stanley; Bao, Zongnan; Forets, Marcelo; Frehse, Goran; Freire, Daniel; Kochdumper, Niklas; Li, Yangge; Mitra, Sayan; Ray, Rajarshi; Schilling, Christian; Schupp, Stefan; et al. (EPiC Series in Computing)
We present the results of the ARCH 2020 friendly competition for formal verification of continuous and hybrid systems with linear continuous dynamics. In its fourth edition, eight tools have been applied to solve eight different benchmark problems in the category for linear continuous dynamics (in alphabetical order): CORA, C2E2, HyDRA, Hylaa, Hylaa-Continuous, JuliaReach, SpaceEx, and XSpeed. This report is a snapshot of the current landscape of tools and the types of benchmarks they are particularly suited for. Due to the diversity of problems, we are not ranking tools, yet the presented results provide one of the most complete assessments of tools for the safety verification of continuous and hybrid systems with linear continuous dynamics up to this date.

ARCH-COMP20 Category Report: Continuous and hybrid systems with nonlinear dynamics - Geretti, Luca; Alexandre Dit Sandretto, Julien; Althoff, Matthias; Benet, Luis; Chapoutot, Alexandre; Chen, Xin; Collins, Pieter; Forets, Marcelo; Freire, Daniel; Immler, Fabian; Kochdumper, Niklas; Sanders, David; et al. (EPiC Series in Computing)
We present the results of a friendly competition for formal verification of continuous and hybrid systems with nonlinear continuous dynamics. The friendly competition took place as part of the workshop Applied Verification for Continuous and Hybrid Systems (ARCH) in 2020. This year, 6 tools Ariadne, CORA, DynIbex, Flow*, Isabelle/HOL, and JuliaReach (in alphabetic order) participated. These tools are applied to solve reachability analysis problems on six benchmark problems, two of them featuring hybrid dynamics. We do not rank the tools based on the results, but show the current status and discover the potential advantages of different tools.

Multi-dimensional long-run average problems for vector addition systems with states - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan (31st International Conference on Concurrency Theory)
A vector addition system with states (VASS) consists of a finite set of states and counters. A transition changes the current state to the next state, and every counter is either incremented, or decremented, or left unchanged. A state and value for each counter is a configuration; and a computation is an infinite sequence of configurations with transitions between successive configurations. A probabilistic VASS consists of a VASS along with a probability distribution over the transitions for each state. Qualitative properties such as state and configuration reachability have been widely studied for VASS. In this work we consider multi-dimensional long-run average objectives for VASS and probabilistic VASS. For a counter, the cost of a configuration is the value of the counter; and the long-run average value of a computation for the counter is the long-run average of the costs of the configurations in the computation. The multi-dimensional long-run average problem given a VASS and a threshold value for each counter, asks whether there is a computation such that for each counter the long-run average value for the counter does not exceed the respective threshold. For probabilistic VASS, instead of the existence of a computation, we consider whether the expected long-run average value for each counter does not exceed the respective threshold. Our main results are as follows: we show that the multi-dimensional long-run average problem (a) is NP-complete for integer-valued VASS; (b) is undecidable for natural-valued VASS (i.e., nonnegative counters); and (c) can be solved in polynomial time for probabilistic integer-valued VASS, and probabilistic natural-valued VASS when all computations are non-terminating.

A survey of bidding games on graphs - Avni, Guy; Henzinger, Thomas A (31st International Conference on Concurrency Theory)
A graph game is a two-player zero-sum game in which the players move a token throughout a graph to produce an infinite path, which determines the winner or payoff of the game. In bidding games, both players have budgets, and in each turn, we hold an "auction" (bidding) to determine which player moves the token. In this survey, we consider several bidding mechanisms and study their effect on the properties of the game. Specifically, bidding games, and in particular bidding games of infinite duration, have an intriguing equivalence with random-turn games in which in each turn, the player who moves is chosen randomly. We show how minor changes in the bidding mechanism lead to unexpected differences in the equivalence with random-turn games.

The splay-list: A distribution-adaptive concurrent skip-list - Aksenov, Vitaly; Alistarh, Dan-Adrian; Drozdova, Alexandra; Mohtashami, Amirkeivan (34th International Symposium on Distributed Computing)
The design and implementation of efficient concurrent data structures have seen significant attention. However, most of this work has focused on concurrent data structures providing good worst-case guarantees. In real workloads, objects are often accessed at different rates, since access distributions may be non-uniform. Efficient distribution-adaptive data structures are known in the sequential case, e.g. the splay-trees; however, they often are hard to translate efficiently in the concurrent case. In this paper, we investigate distribution-adaptive concurrent data structures and propose a new design called the splay-list. At a high level, the splay-list is similar to a standard skip-list, with the key distinction that the height of each element adapts dynamically to its access rate: popular elements ``move up,'' whereas rarely-accessed elements decrease in height. We show that the splay-list provides order-optimal amortized complexity bounds for a subset of operations while being amenable to efficient concurrent implementation. Experimental results show that the splay-list can leverage distribution-adaptivity to improve on the performance of classic concurrent designs, and can outperform the only previously-known distribution-adaptive design in certain settings.

Evolution of spin-orbital entanglement with increasing ising spin-orbit coupling - Gotfryd, Dorota; Paerschke, Ekaterina; Wohlfeld, Krzysztof; Oleś, Andrzej M. (Condensed Matter)
Several realistic spin-orbital models for transition metal oxides go beyond the classical expectations and could be understood only by employing the quantum entanglement. Experiments on these materials confirm that spin-orbital entanglement has measurable consequences. Here, we capture the essential features of spin-orbital entanglement in complex quantum matter utilizing 1D spin-orbital model which accommodates SU(2)⊗SU(2) symmetric Kugel-Khomskii superexchange as well as the Ising on-site spin-orbit coupling. Building on the results obtained for full and effective models in the regime of strong spin-orbit coupling, we address the question whether the entanglement found on superexchange bonds always increases when the Ising spin-orbit coupling is added. We show that (i) quantum entanglement is amplified by strong spin-orbit coupling and, surprisingly, (ii) almost classical disentangled states are possible. We complete the latter case by analyzing how the entanglement existing for intermediate values of spin-orbit coupling can disappear for higher values of this coupling.

Formal methods with a touch of magic - Alamdari, Par Alizadeh; Avni, Guy; Henzinger, Thomas A; Lukina, Anna (Proceedings of the 20th Conference on Formal Methods in Computer-Aided Design)
Machine learning and formal methods have complimentary benefits and drawbacks. In this work, we address the controller-design problem with a combination of techniques from both fields. The use of black-box neural networks in deep reinforcement learning (deep RL) poses a challenge for such a combination. Instead of reasoning formally about the output of deep RL, which we call the wizard, we extract from it a decision-tree based model, which we refer to as the magic book. Using the extracted model as an intermediary, we are able to handle problems that are infeasible for either deep RL or formal methods by themselves. First, we suggest, for the first time, a synthesis procedure that is based on a magic book. We synthesize a stand-alone correct-by-design controller that enjoys the favorable performance of RL. Second, we incorporate a magic book in a bounded model checking (BMC) procedure. BMC allows us to find numerous traces of the plant under the control of the wizard, which a user can use to increase the trustworthiness of the wizard and direct further training.

What controls the water vapor isotopic composition near the surface of tropical oceans? Results from an analytical model constrained by large‐eddy simulations - Risi, Camille; Muller, Caroline J; Blossey, Peter (Journal of Advances in Modeling Earth Systems)
The goal of this study is to understand the mechanisms controlling the isotopic composition of the water vapor near the surface of tropical oceans, at the scale of about a hundred kilometers and a month. In the tropics, it has long been observed that the isotopic compositions of rain and vapor near the surface are more depleted when the precipitation rate is high. This is called the “amount effect.” Previous studies, based on observations or models with parameterized convection, have highlighted the roles of deep convective and mesoscale downdrafts and rain evaporation. But the relative importance of these processes has never been quantified. We hypothesize that it can be quantified using an analytical model constrained by large‐eddy simulations. Results from large‐eddy simulations confirm that the classical amount effect can be simulated only if precipitation rate changes result from changes in the large‐scale circulation. We find that the main process depleting the water vapor compared to the equilibrium with the ocean is the fact that updrafts stem from areas where the water vapor is more enriched. The main process responsible for the amount effect is the fact that when the large‐scale ascent increases, isotopic vertical gradients are steeper, so that updrafts and downdrafts deplete the subcloud layer more efficiently.
Keywords: Global and Planetary Change; General Earth and Planetary Sciences; Environmental Chemistry

How warmer and drier will the Mediterranean region be at the end of the twenty-first century? - Drobinski, Philippe; Da Silva, Nicolas; Bastin, Sophie; Mailler, Sylvain; Muller, Caroline J; Ahrens, Bodo; Christensen, Ole B.; Lionello, Piero (Regional Environmental Change)
Nearly all regions in the world are projected to become dryer in a warming climate. Here, we investigate the Mediterranean region, often referred to as a climate change “hot spot”. From regional climate simulations, it is shown that although enhanced warming and drying over land is projected, the spatial pattern displays high variability. Indeed, drying is largely caused by enhanced warming over land. However, in Northern Europe, soil moisture alleviates warming induced drying by up to 50% due to humidity uptake from land. In already arid regions, the Mediterranean Sea is generally the only humidity source, and drying is only due to land warming. However, over Sahara and the Iberian Peninsula, enhanced warming over land is insufficient to explain the extreme drying. These regions are also isolated from humidity advection by heat lows, which are cyclonic circulation anomalies associated with surface heating over land. The cyclonic circulation scales with the temperature gradient between land and ocean which increases with climate change, reinforcing the cyclonic circulation over Sahara and the Iberian Peninsula, both diverting the zonal advection of humidity to the south of the Iberian Peninsula. The dynamics are therefore key in the warming and drying of the Mediterranean region, with extreme aridification over the Sahara and Iberian Peninsula. In these regions, the risk for human health due to the thermal load which accounts for air temperature and humidity is therefore projected to increase significantly with climate change at a level of extreme danger.
Keywords: Global and Planetary Change

Response of precipitation extremes to warming: What have we learned from theory and idealized cloud-resolving simulations, and what remains to be learned? - Muller, Caroline J; Takayabu, Yukari (Environmental Research Letters)
This paper reviews recent important advances in our understanding of the response of precipitation extremes to warming from theory and from idealized cloud-resolving simulations. A theoretical scaling for precipitation extremes has been proposed and refined in the past decades, allowing to address separately the contributions from the thermodynamics, the dynamics and the microphysics. Theoretical constraints, as well as remaining uncertainties, associated with each of these three contributions to precipitation extremes, are discussed. Notably, although to leading order precipitation extremes seem to follow the thermodynamic theoretical expectation in idealized simulations, considerable uncertainty remains regarding the response of the dynamics and of the microphysics to warming, and considerable departure from this theoretical expectation is found in observations and in more realistic simulations. We also emphasize key outstanding questions, in particular the response of mesoscale convective organization to warming. Observations suggest that extreme rainfall often comes from an organized system in very moist environments. Improved understanding of the physical processes behind convective organization is needed in order to achieve accurate extreme rainfall prediction in our current, and in a warming climate.
Keywords: Renewable Energy; Sustainability and the Environment; Public Health; Environmental and Occupational Health; General Environmental Science

Self‐aggregation of convective clouds with interactive sea surface temperature - Shamekh, S.; Muller, Caroline J; Duvel, J.‐P.; D'Andrea, F. (Journal of Advances in Modeling Earth Systems)
This study investigates the feedbacks between an interactive sea surface temperature (SST) and the self‐aggregation of deep convective clouds, using a cloud‐resolving model in nonrotating radiative‐convective equilibrium. The ocean is modeled as one layer slab with a temporally fixed mean but spatially varying temperature. We find that the interactive SST decelerates the aggregation and that the deceleration is larger with a shallower slab, consistent with earlier studies. The surface temperature anomaly in dry regions is positive at first, thus opposing the diverging shallow circulation known to favor self‐aggregation, consistent with the slower aggregation. But surprisingly, the driest columns then have a negative SST anomaly, thus strengthening the diverging shallow circulation and favoring aggregation. This diverging circulation out of dry regions is found to be well correlated with the aggregation speed. It can be linked to a positive surface pressure anomaly (PSFC), itself the consequence of SST anomalies and boundary layer radiative cooling. The latter cools and dries the boundary layer, thus increasing PSFC anomalies through virtual effects and hydrostasy. Sensitivity experiments confirm the key role played by boundary layer radiative cooling in determining PSFC anomalies in dry regions, and thus the shallow diverging circulation and the aggregation speed.
Keywords: Global and Planetary Change; General Earth and Planetary Sciences; Environmental Chemistry

Atmospheric radiative profiles during EUREC4A - Albright, Anna Lea; Fildier, Benjamin; Touzé-Peiffer, Ludovic; Pincus, Robert; Vial, Jessica; Muller, Caroline J (Earth System Science Data)
The couplings among clouds, convection, and circulation in trade-wind regimes remain a fundamental puzzle that limits our ability to constrain future climate change. Radiative heating plays an important role in these couplings. Here we calculate the clear-sky radiative profiles from 2001 in-situ soundings (978 dropsondes and 1023 radiosondes) collected during the EUREC4A field campaign, which took place south and east of Barbados in January–February 2020. We describe the method used to calculate these radiative profiles and present preliminary results sampling variability at multiple scales, from the variability across all soundings to groupings by diurnal cycle and mesoscale organization state, as well as individual soundings associated with elevated moisture layers. This clear-sky radiative profiles data set can provide important missing detail to what can be learned from calculations based on passive remote sensing and help in investigating the role of radiation in dynamic and thermodynamic variability in trade-wind regimes. All data are archived and freely available for public access on AERIS (Albright et al. (2020), https://doi.org/10.25326/78).

Decision-making at a T-junction by gradient-sensing microscopic agents - Gandhi, Tanvi; Mac Huang, Jinzi; Aubret, Antoine; Li, Yaocheng; Ramananarivo, Sophie; Vergassola, Massimo; Palacci, Jérémie A (Physical Review Fluids)
Active navigation relies on effectively extracting information from the surrounding environment, and often features the tracking of gradients of a relevant signal—such as the concentration of molecules. Microfluidic networks of closed pathways pose the challenge of determining the shortest exit pathway, which involves the proper local decision-making at each bifurcating junction. Here, we focus on the basic decision faced at a T-junction by a microscopic particle, which orients among possible paths via its sensing of a diffusible substance's concentration. We study experimentally the navigation of colloidal particles following concentration gradients by diffusiophoresis. We treat the situation as a mean first passage time (MFPT) problem that unveils the important role of a separatrix in the concentration field to determine the statistics of path taking. Further, we use numerical experiments to study different strategies, including biomimetic ones such as run and tumble or Markovian chemotactic migration. The discontinuity in the MFPT at the junction makes it remarkably difficult for microscopic agents to follow the shortest path, irrespective of adopted navigation strategy. In contrast, increasing the size of the sensing agents improves the efficiency of short-path taking by harvesting information on a larger scale. It inspires the development of a run-and-whirl dynamics that takes advantage of the mathematical properties of harmonic functions to emulate particles beyond their own size.

Focus on active colloids and nanoparticles - Speck, Thomas; Tailleur, Julien; Palacci, Jérémie A (New Journal of Physics)
Keywords: General Physics and Astronomy

Digital objects in rhombic dodecahedron grid - Biswas, Ranita; Largeteau-Skapin, Gaëlle; Zrour, Rita; Andres, Eric (Mathematical Morphology - Theory and Applications)
Rhombic dodecahedron is a space filling polyhedron which represents the close packing of spheres in 3D space and the Voronoi structures of the face centered cubic (FCC) lattice. In this paper, we describe a new coordinate system where every 3-integer coordinates grid point corresponds to a rhombic dodecahedron centroid. In order to illustrate the interest of the new coordinate system, we propose the characterization of 3D digital plane with its topological features, such as the interrelation between the thickness of the digital plane and the separability constraint we aim to obtain. We also present the characterization of 3D digital lines and study it as the intersection of multiple digital planes. Characterization of 3D digital sphere with relevant topological features is proposed as well along with the 48-symmetry appearing in the new coordinate system.

Crossings between non-homotopic edges - Pach, János; Tardos, Gábor; Tóth, Géza (28th International Symposium on Graph Drawing and Network Visualization)
We call a multigraph non-homotopic if it can be drawn in the plane in such a way that no two edges connecting the same pair of vertices can be continuously transformed into each other without passing through a vertex, and no loop can be shrunk to its end-vertex in the same way. It is easy to see that a non-homotopic multigraph on n>1 vertices can have arbitrarily many edges. We prove that the number of crossings between the edges of a non-homotopic multigraph with n vertices and m>4n edges is larger than cm2n for some constant c>0 , and that this bound is tight up to a polylogarithmic factor. We also show that the lower bound is not asymptotically sharp as n is fixed and m⟶∞ .

Halfway to Rota’s basis conjecture - Bucić, Matija; Kwan, Matthew Alan; Pokrovskiy, Alexey; Sudakov, Benny (International Mathematics Research Notices)
In 1989, Rota made the following conjecture. Given n bases B1,…,Bn in an n-dimensional vector space V⁠, one can always find n disjoint bases of V⁠, each containing exactly one element from each Bi (we call such bases transversal bases). Rota’s basis conjecture remains wide open despite its apparent simplicity and the efforts of many researchers (e.g., the conjecture was recently the subject of the collaborative “Polymath” project). In this paper we prove that one can always find (1/2−o(1))n disjoint transversal bases, improving on the previous best bound of Ω(n/logn)⁠. Our results also apply to the more general setting of matroids.

Ramsey graphs induce subgraphs of quadratically many sizes - Kwan, Matthew Alan; Sudakov, Benny (International Mathematics Research Notices)
An n-vertex graph is called C-Ramsey if it has no clique or independent set of size Clogn⁠. All known constructions of Ramsey graphs involve randomness in an essential way, and there is an ongoing line of research towards showing that in fact all Ramsey graphs must obey certain “richness” properties characteristic of random graphs. Motivated by an old problem of Erd̋s and McKay, recently Narayanan, Sahasrabudhe, and Tomon conjectured that for any fixed C, every n-vertex C-Ramsey graph induces subgraphs of Θ(n2) different sizes. In this paper we prove this conjecture.

Universality of random permutations - He, Xiaoyu; Kwan, Matthew Alan (Bulletin of the London Mathematical Society)
It is a classical fact that for any ε>0, a random permutation of length n=(1+ε)k2/4 typically contains a monotone subsequence of length k. As a far-reaching generalization, Alon conjectured that a random permutation of this same length n is typically k-universal, meaning that it simultaneously contains every pattern of length k. He also made the simple observation that for n=O(k2logk), a random length-n permutation is typically k-universal. We make the first significant progress towards Alon's conjecture by showing that n=2000k2loglogk suffices.

WoodFisher: Efficient second-order approximation for neural network compression - Singh, Sidak Pal; Alistarh, Dan-Adrian (Advances in Neural Information Processing Systems)
Second-order information, in the form of Hessian- or Inverse-Hessian-vector products, is a fundamental tool for solving optimization problems. Recently, there has been significant interest in utilizing this information in the context of deep neural networks; however, relatively little is known about the quality of existing approximations in this context. Our work examines this question, identifies issues with existing approaches, and proposes a method called WoodFisher to compute a faithful and efficient estimate of the inverse Hessian. Our main application is to neural network compression, where we build on the classic Optimal Brain Damage/Surgeon framework. We demonstrate that WoodFisher significantly outperforms popular state-of-the-art methods for oneshot pruning. Further, even when iterative, gradual pruning is allowed, our method results in a gain in test accuracy over the state-of-the-art approaches, for standard image classification datasets such as ImageNet ILSVRC. We examine how our method can be extended to take into account first-order information, as well as illustrate its ability to automatically set layer-wise pruning thresholds and perform compression in the limited-data regime. The code is available at the following link, https://github.com/IST-DASLab/WoodFisher.

Topological data analysis in information space - Edelsbrunner, Herbert; Virk, Ziga; Wagner, Hubert (Journal of Computational Geometry)
Various kinds of data are routinely represented as discrete probability distributions. Examples include text documents summarized by histograms of word occurrences and images represented as histograms of oriented gradients. Viewing a discrete probability distribution as a point in the standard simplex of the appropriate dimension, we can understand collections of such objects in geometric and topological terms. Importantly, instead of using the standard Euclidean distance, we look into dissimilarity measures with information-theoretic justification, and we develop the theory needed for applying topological data analysis in this setting. In doing so, we emphasize constructions that enable the usage of existing computational topology software in this context.

Scalable belief propagation via relaxed scheduling - Aksenov, Vitaly; Alistarh, Dan-Adrian; Korhonen, Janne (Advances in Neural Information Processing Systems)
The ability to leverage large-scale hardware parallelism has been one of the key enablers of the accelerated recent progress in machine learning. Consequently, there has been considerable effort invested into developing efficient parallel variants of classic machine learning algorithms. However, despite the wealth of knowledge on parallelization, some classic machine learning algorithms often prove hard to parallelize efficiently while maintaining convergence. In this paper, we focus on efficient parallel algorithms for the key machine learning task of inference on graphical models, in particular on the fundamental belief propagation algorithm. We address the challenge of efficiently parallelizing this classic paradigm by showing how to leverage scalable relaxed schedulers in this context. We present an extensive empirical study, showing that our approach outperforms previous parallel belief propagation implementations both in terms of scalability and in terms of wall-clock convergence time, on a range of practical applications.

Predicting the phase diagram of titanium dioxide with random search and pattern recognition - Reinhardt, Aleks; Pickard, Chris J.; Cheng, Bingqing (Physical Chemistry Chemical Physics)
Predicting phase stabilities of crystal polymorphs is central to computational materials science and chemistry. Such predictions are challenging because they first require searching for potential energy minima and then performing arduous free-energy calculations to account for entropic effects at finite temperatures. Here, we develop a framework that facilitates such predictions by exploiting all the information obtained from random searches of crystal structures. This framework combines automated clustering, classification and visualisation of crystal structures with machine-learning estimation of their enthalpy and entropy. We demonstrate the framework on the technologically important system of TiO2, which has many polymorphs, without relying on prior knowledge of known phases. We find a number of new phases and predict the phase diagram and metastabilities of crystal polymorphs at 1600 K, benchmarking the results against full free-energy calculations.

Liquid water contains the building blocks of diverse ice phases - Monserrat, Bartomeu; Brandenburg, Jan Gerit; Engel, Edgar A.; Cheng, Bingqing (Nature Communications)
Water molecules can arrange into a liquid with complex hydrogen-bond networks and at least 17 experimentally confirmed ice phases with enormous structural diversity. It remains a puzzle how or whether this multitude of arrangements in different phases of water are related. Here we investigate the structural similarities between liquid water and a comprehensive set of 54 ice phases in simulations, by directly comparing their local environments using general atomic descriptors, and also by demonstrating that a machine-learning potential trained on liquid water alone can predict the densities, lattice energies, and vibrational properties of the ices. The finding that the local environments characterising the different ice phases are found in water sheds light on the phase behavior of water, and rationalizes the transferability of water models between different phases.

Simplified game of life: Algorithms and complexity - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Jecker, Ismael R; Svoboda, Jakub (45th International Symposium on Mathematical Foundations of Computer Science)
Game of Life is a simple and elegant model to study dynamical system over networks. The model consists of a graph where every vertex has one of two types, namely, dead or alive. A configuration is a mapping of the vertices to the types. An update rule describes how the type of a vertex is updated given the types of its neighbors. In every round, all vertices are updated synchronously, which leads to a configuration update. While in general, Game of Life allows a broad range of update rules, we focus on two simple families of update rules, namely, underpopulation and overpopulation, that model several interesting dynamics studied in the literature. In both settings, a dead vertex requires at least a desired number of live neighbors to become alive. For underpopulation (resp., overpopulation), a live vertex requires at least (resp. at most) a desired number of live neighbors to remain alive. We study the basic computation problems, e.g., configuration reachability, for these two families of rules. For underpopulation rules, we show that these problems can be solved in polynomial time, whereas for overpopulation rules they are PSPACE-complete.

Unary prime languages - Jecker, Ismael R; Kupferman, Orna; Mazzocchi, Nicolas (45th International Symposium on Mathematical Foundations of Computer Science)
A regular language L of finite words is composite if there are regular languages L₁,L₂,…,L_t such that L = ⋂_{i = 1}^t L_i and the index (number of states in a minimal DFA) of every language L_i is strictly smaller than the index of L. Otherwise, L is prime. Primality of regular languages was introduced and studied in [O. Kupferman and J. Mosheiff, 2015], where the complexity of deciding the primality of the language of a given DFA was left open, with a doubly-exponential gap between the upper and lower bounds. We study primality for unary regular languages, namely regular languages with a singleton alphabet. A unary language corresponds to a subset of ℕ, making the study of unary prime languages closer to that of primality in number theory. We show that the setting of languages is richer. In particular, while every composite number is the product of two smaller numbers, the number t of languages necessary to decompose a composite unary language induces a strict hierarchy. In addition, a primality witness for a unary language L, namely a word that is not in L but is in all products of languages that contain L and have an index smaller than L’s, may be of exponential length. Still, we are able to characterize compositionality by structural properties of a DFA for L, leading to a LogSpace algorithm for primality checking of unary DFAs.

Billiards in ellipses revisited - Akopyan, Arseniy; Schwartz, Richard; Tabachnikov, Serge (European Journal of Mathematics)
We prove some recent experimental observations of Dan Reznik concerning periodic billiard orbits in ellipses. For example, the sum of cosines of the angles of a periodic billiard polygon remains constant in the 1-parameter family of such polygons (that exist due to the Poncelet porism). In our proofs, we use geometric and complex analytic methods.

Reduction of neuronal activity mediated by blood-vessel regression in the brain - Gao, Xiaofei; Li, Jun-Liszt; Chen, Xingjun; Ci, Bo; Chen, Fei; Lu, Nannan; Shen, Bo; Zheng, Lijun; Jia, Jie-Min; Yi, Yating; Zhang, Shiwen; Shi, Ying-Chao; et al. (bioRxiv)
The brain vasculature supplies neurons with glucose and oxygen, but little is known about how vascular plasticity contributes to brain function. Using longitudinal in vivo imaging, we reported that a substantial proportion of blood vessels in the adult brain sporadically occluded and regressed. Their regression proceeded through sequential stages of blood-flow occlusion, endothelial cell collapse, relocation or loss of pericytes, and retraction of glial endfeet. Regressing vessels were found to be widespread in mouse, monkey and human brains. Both brief occlusions of the middle cerebral artery and lipopolysaccharide-mediated inflammation induced an increase of vessel regression. Blockage of leukocyte adhesion to endothelial cells alleviated LPS-induced vessel regression. We further revealed that blood vessel regression caused a reduction of neuronal activity due to a dysfunction in mitochondrial metabolism and glutamate production. Our results elucidate the mechanism of vessel regression and its role in neuronal function in the adult brain.

Empfehlungen für eine nationale Open Science Strategie in Österreich / Recommendations for a National Open Science Strategy in Austria - Mayer, Katja; Rieck, Katharina; Reichmann, Stefan; Danowski, Patrick; Graschopf, Anton; König, Thomas; Kraker, Peter; Lehner, Patrick; Reckling, Falk; Ross-Hellauer, Tony; Spichtinger, Daniel; Tzatzanis, Michalis; et al.
A look at international activities on Open Science reveals a broad spectrum from individual institutional policies to national action plans. The present Recommendations for a National Open Science Strategy in Austria are based on these international initiatives and present practical considerations for their coordinated implementation with regard to strategic developments in research, technology and innovation (RTI) in Austria until 2030. They are addressed to all relevant actors in the RTI system, in particular to Research Performing Organisations, Research Funding Organisations, Research Policy, memory institutions such as Libraries and Researchers. The recommendation paper was developed from 2018 to 2020 by the OANA working group "Open Science Strategy" and published for the first time in spring 2020 for a public consultation. The now available final version of the recommendation document, which contains feedback and comments from the consultation, is intended to provide an impetus for further discussion and implementation of Open Science in Austria and serves as a contribution and basis for a potential national Open Science Strategy in Austria. The document builds on the diverse expertise of the authors (academia, administration, library and archive, information technology, science policy, funding system, etc.) and reflects their personal experiences and opinions.

Rigorous numerics for critical orbits in the quadratic family - Golmakani, Ali; Koudjinan, Edmond; Luzzatto, Stefano; Pilarczyk, Pawel (Chaos)
We develop algorithms and techniques to compute rigorous bounds for finite pieces of orbits of the critical points, for intervals of parameter values, in the quadratic family of one-dimensional maps fa(x)=a−x2. We illustrate the effectiveness of our approach by constructing a dynamically defined partition 𝒫 of the parameter interval Ω=[1.4,2] into almost 4×106 subintervals, for each of which we compute to high precision the orbits of the critical points up to some time N and other dynamically relevant quantities, several of which can vary greatly, possibly spanning several orders of magnitude. We also subdivide 𝒫 into a family 𝒫+ of intervals, which we call stochastic intervals, and a family 𝒫− of intervals, which we call regular intervals. We numerically prove that each interval ω∈𝒫+ has an escape time, which roughly means that some iterate of the critical point taken over all the parameters in ω has considerable width in the phase space. This suggests, in turn, that most parameters belonging to the intervals in 𝒫+ are stochastic and most parameters belonging to the intervals in 𝒫− are regular, thus the names. We prove that the intervals in 𝒫+ occupy almost 90% of the total measure of Ω. The software and the data are freely available at http://www.pawelpilarczyk.com/quadr/, and a web page is provided for carrying out the calculations. The ideas and procedures can be easily generalized to apply to other parameterized families of dynamical systems.

A KAM theorem for finitely differentiable Hamiltonian systems - Koudjinan, Edmond (Journal of Differential Equations)
Given l>2ν>2d≥4, we prove the persistence of a Cantor--family of KAM tori of measure O(ε1/2−ν/l) for any non--degenerate nearly integrable Hamiltonian system of class Cl(D×Td), where D⊂Rd is a bounded domain, provided that the size ε of the perturbation is sufficiently small. This extends a result by D. Salamon in \cite{salamon2004kolmogorov} according to which we do have the persistence of a single KAM torus in the same framework. Moreover, it is well--known that, for the persistence of a single torus, the regularity assumption can not be improved.
Keywords: Analysis

„Recommendation“ for the further procedure for open access monitoring. Deliverable of the AT2OA subproject TP1-B - Danowski, Patrick; Ferus, Andreas; Hikl, Anna-Laetitia; McNeill, Gerda; Miniberger, Clemens; Reding, Steve; Zarka, Tobias; Zojer, Michael (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare)
As part of the Austrian Transition to Open Access (AT2OA) project, subproject TP1-B is working on designing a monitoring solution for the output of Open Access publications in Austria. This report on a potential Open Access monitoring approach in Austria is one of the results of these efforts and can serve as a basis for discussion on an international level.

Generation and isolation of single cells from mouse brain with mosaic analysis with double markers-induced uniparental chromosome disomy - Laukoter, Susanne; Amberg, Nicole; Pauler, Florian; Hippenmeyer, Simon (STAR Protocols)
Mosaic analysis with double markers (MADM) technology enables concomitant fluorescent cell labeling and induction of uniparental chromosome disomy (UPD) with single-cell resolution. In UPD, imprinted genes are either overexpressed 2-fold or are not expressed. Here, the MADM platform is utilized to probe imprinting phenotypes at the transcriptional level. This protocol highlights major steps for the generation and isolation of projection neurons and astrocytes with MADM-induced UPD from mouse cerebral cortex for downstream single-cell and low-input sample RNA-sequencing experiments. For complete details on the use and execution of this protocol, please refer to Laukoter et al. (2020b).

Size-dependent magnetic and magnetothermal properties of gadolinium silicide nanoparticles - Nauman, Muhammad; Alnasir, Muhammad Hisham; Hamayun, Muhammad Asif; Wang, YiXu; Shatruk, Michael; Manzoor, Sadia (RSC Advances)
Gadolinium silicide (Gd5Si4) nanoparticles are an interesting class of materials due to their high magnetization, low Curie temperature, low toxicity in biological environments and their multifunctional properties. We report the magnetic and magnetothermal properties of gadolinium silicide (Gd5Si4) nanoparticles prepared by surfactant-assisted ball milling of arc melted bulk ingots of the compound. Using different milling times and speeds, a wide range of crystallite sizes (13–43 nm) could be produced and a reduction in Curie temperature (TC) from 340 K to 317 K was achieved, making these nanoparticles suitable for self-controlled magnetic hyperthermia applications. The magnetothermal effect was measured in applied AC magnetic fields of amplitude 164–239 Oe and frequencies 163–519 kHz. All particles showed magnetic heating with a strong dependence of the specific absorption rate (SAR) on the average crystallite size. The highest SAR of 3.7 W g−1 was measured for 43 nm sized nanoparticles of Gd5Si4. The high SAR and low TC, (within the therapeutic range for magnetothermal therapy) makes the Gd5Si4 behave like self-regulating heat switches that would be suitable for self-controlled magnetic hyperthermia applications after biocompatibility and cytotoxicity tests.
Keywords: General Chemistry; General Chemical Engineering

Lagrangian reachtubes: The next generation - Gruenbacher, Sophie; Cyranka, Jacek; Lechner, Mathias; Islam, Md Ariful; Smolka, Scott A.; Grosu, Radu (Proceedings of the 59th IEEE Conference on Decision and Control)
We introduce LRT-NG, a set of techniques and an associated toolset that computes a reachtube (an over-approximation of the set of reachable states over a given time horizon) of a nonlinear dynamical system. LRT-NG significantly advances the state-of-the-art Langrangian Reachability and its associated tool LRT. From a theoretical perspective, LRT-NG is superior to LRT in three ways. First, it uses for the first time an analytically computed metric for the propagated ball which is proven to minimize the ball’s volume. We emphasize that the metric computation is the centerpiece of all bloating-based techniques. Secondly, it computes the next reachset as the intersection of two balls: one based on the Cartesian metric and the other on the new metric. While the two metrics were previously considered opposing approaches, their joint use considerably tightens the reachtubes. Thirdly, it avoids the "wrapping effect" associated with the validated integration of the center of the reachset, by optimally absorbing the interval approximation in the radius of the next ball. From a tool-development perspective, LRT-NG is superior to LRT in two ways. First, it is a standalone tool that no longer relies on CAPD. This required the implementation of the Lohner method and a Runge-Kutta time-propagation method. Secondly, it has an improved interface, allowing the input model and initial conditions to be provided as external input files. Our experiments on a comprehensive set of benchmarks, including two Neural ODEs, demonstrates LRT-NG’s superior performance compared to LRT, CAPD, and Flow*.

Rain evaporation, snow melt and entrainment at the heart of water vapor isotopic variations in the tropical troposphere, according to large-eddy simulations and a two-column model - Risi, Camille; Muller, Caroline J; Blossey, Peter N.
The goal of this study is twofold. First, we aim at developing a simple model as an interpretative framework for the water vapor isotopic variations in the tropical troposphere over the ocean. We use large-eddy simulations to justify the underlying assumptions of this simple model, to constrain its input parameters and to evaluate its results. Second, we aim at interpreting the depletion of the water vapor isotopic composition in the lower and mid-troposphere as precipitation increases, which is a salient feature in tropical oceanic observations. This feature constitutes a stringent test on the relevance of our interpretative framework. Previous studies, based on observations or on models with parameterized convection, have highlighted the roles of deep convective and meso-scale downdrafts, rain evaporation, rain-vapor diffusive exchanges and mixing processes. The interpretative framework that we develop is a two-column model representing the net ascent in clouds and the net descent in the environment. We show that the mechanisms for depleting the troposphere when precipitation rate increases all stem from the higher tropospheric relative humidity. First, when the relative humidity is larger, less snow sublimates before melting and a smaller fraction of rain evaporates. Both effects lead to more depleted rain evaporation and eventually more depleted water vapor. This mechanism dominates in regimes of large-scale ascent. Second, the entrainment of dry air into clouds reduces the vertical isotopic gradient and limits the depletion of tropospheric water vapor. This mechanism dominates in regimes of large-scale descent.

Global convergence of deep networks with one wide layer followed by pyramidal topology - Nguyen, Quynh; Mondelli, Marco (34th Conference on Neural Information Processing Systems)
Recent works have shown that gradient descent can find a global minimum for over-parameterized neural networks where the widths of all the hidden layers scale polynomially with N (N being the number of training samples). In this paper, we prove that, for deep networks, a single layer of width N following the input layer suffices to ensure a similar guarantee. In particular, all the remaining layers are allowed to have constant widths, and form a pyramidal topology. We show an application of our result to the widely used LeCun’s initialization and obtain an over-parameterization requirement for the single wide layer of order N2.

Inducing and exploiting activation sparsity for fast neural network inference - Kurtz, Mark; Kopinsky, Justin; Gelashvili, Rati; Matveev, Alexander; Carr, John; Goin, Michael; Leiserson, William; Moore, Sage; Nell, Bill; Shavit, Nir; Alistarh, Dan-Adrian (37th International Conference on Machine Learning, ICML 2020)
Optimizing convolutional neural networks for fast inference has recently become an extremely active area of research. One of the go-to solutions in this context is weight pruning, which aims to reduce computational and memory footprint by removing large subsets of the connections in a neural network. Surprisingly, much less attention has been given to exploiting sparsity in the activation maps, which tend to be naturally sparse in many settings thanks to the structure of rectified linear (ReLU) activation functions. In this paper, we present an in-depth analysis of methods for maximizing the sparsity of the activations in a trained neural network, and show that, when coupled with an efficient sparse-input convolution algorithm, we can leverage this sparsity for significant performance gains. To induce highly sparse activation maps without accuracy loss, we introduce a new regularization technique, coupled with a new threshold-based sparsification method based on a parameterized activation function called Forced-Activation-Threshold Rectified Linear Unit (FATReLU). We examine the impact of our methods on popular image classification models, showing that most architectures can adapt to significantly sparser activation maps without any accuracy loss. Our second contribution is showing that these these compression gains can be translated into inference speedups: we provide a new algorithm to enable fast convolution operations over networks with sparse activations, and show that it can enable significant speedups for end-to-end inference on a range of popular models on the large-scale ImageNet image classification task on modern Intel CPUs, with little or no retraining cost.

DNA methylation and histone H1 jointly repress transposable elements and aberrant intragenic transcripts - Choi, Jaemyung; Lyons, David B.; Kim, M. Yvonne; Moore, Jonathan D.; Zilberman, Daniel (Molecular Cell)
DNA methylation and histone H1 mediate transcriptional silencing of genes and transposable elements, but how they interact is unclear. In plants and animals with mosaic genomic methylation, functionally mysterious methylation is also common within constitutively active housekeeping genes. Here, we show that H1 is enriched in methylated sequences, including genes, of Arabidopsis thaliana, yet this enrichment is independent of DNA methylation. Loss of H1 disperses heterochromatin, globally alters nucleosome organization, and activates H1-bound genes, but only weakly de-represses transposable elements. However, H1 loss strongly activates transposable elements hypomethylated through mutation of DNA methyltransferase MET1. Hypomethylation of genes also activates antisense transcription, which is modestly enhanced by H1 loss. Our results demonstrate that H1 and DNA methylation jointly maintain transcriptional homeostasis by silencing transposable elements and aberrant intragenic transcripts. Such functionality plausibly explains why DNA methylation, a well-known mutagen, has been maintained within coding sequences of crucial plant and animal genes.

Almost all Steiner triple systems are almost resolvable - Ferber, Asaf; Kwan, Matthew Alan (Forum of Mathematics)
We show that for any n divisible by 3, almost all order-n Steiner triple systems admit a decomposition of almost all their triples into disjoint perfect matchings (that is, almost all Steiner triple systems are almost resolvable).

Nearly-linear monotone paths in edge-ordered graphs - Bucić, Matija; Kwan, Matthew Alan; Pokrovskiy, Alexey; Sudakov, Benny; Tran, Tuan; Wagner, Adam Zsolt (Israel Journal of Mathematics)
How long a monotone path can one always find in any edge-ordering of the complete graph Kn? This appealing question was first asked by Chvátal and Komlós in 1971, and has since attracted the attention of many researchers, inspiring a variety of related problems. The prevailing conjecture is that one can always find a monotone path of linear length, but until now the best known lower bound was n2/3-o(1). In this paper we almost close this gap, proving that any edge-ordering of the complete graph contains a monotone path of length n1-o(1).

Dense induced bipartite subgraphs in triangle-free graphs - Kwan, Matthew Alan; Letzter, Shoham; Sudakov, Benny; Tran, Tuan (Combinatorica)
The problem of finding dense induced bipartite subgraphs in H-free graphs has a long history, and was posed 30 years ago by Erdős, Faudree, Pach and Spencer. In this paper, we obtain several results in this direction. First we prove that any H-free graph with minimum degree at least d contains an induced bipartite subgraph of minimum degree at least cH log d/log log d, thus nearly confirming one and proving another conjecture of Esperet, Kang and Thomassé. Complementing this result, we further obtain optimal bounds for this problem in the case of dense triangle-free graphs, and we also answer a question of Erdœs, Janson, Łuczak and Spencer.

Almost all Steiner triple systems have perfect matchings - Kwan, Matthew Alan (Proceedings of the London Mathematical Society)
We show that for any 𝑛 divisible by 3, almost all order- 𝑛 Steiner triple systems have a perfect matching (also known as a parallel class or resolution class). In fact, we prove a general upper bound on the number of perfect matchings in a Steiner triple system and show that almost all Steiner triple systems essentially attain this maximum. We accomplish this via a general theorem comparing a uniformly random Steiner triple system to the outcome of the triangle removal process, which we hope will be useful for other problems. Our methods can also be adapted to other types of designs; for example, we sketch a proof of the theorem that almost all Latin squares have transversals.

Classical nucleation theory predicts the shape of the nucleus in homogeneous solidification - Cheng, Bingqing; Ceriotti, Michele; Tribello, Gareth A. (The Journal of Chemical Physics)
Macroscopic models of nucleation provide powerful tools for understanding activated phase transition processes. These models do not provide atomistic insights and can thus sometimes lack material-specific descriptions. Here, we provide a comprehensive framework for constructing a continuum picture from an atomistic simulation of homogeneous nucleation. We use this framework to determine the equilibrium shape of the solid nucleus that forms inside bulk liquid for a Lennard-Jones potential. From this shape, we then extract the anisotropy of the solid-liquid interfacial free energy, by performing a reverse Wulff construction in the space of spherical harmonic expansions. We find that the shape of the nucleus is nearly spherical and that its anisotropy can be perfectly described using classical models.

Computing the heat conductivity of fluids from density fluctuations - Cheng, Bingqing; Frenkel, Daan (Physical Review Letters)
Equilibrium molecular dynamics simulations, in combination with the Green-Kubo (GK) method, have been extensively used to compute the thermal conductivity of liquids. However, the GK method relies on an ambiguous definition of the microscopic heat flux, which depends on how one chooses to distribute energies over atoms. This ambiguity makes it problematic to employ the GK method for systems with nonpairwise interactions. In this work, we show that the hydrodynamic description of thermally driven density fluctuations can be used to obtain the thermal conductivity of a bulk fluid unambiguously, thereby bypassing the need to define the heat flux. We verify that, for a model fluid with only pairwise interactions, our method yields estimates of thermal conductivity consistent with the GK approach. We apply our approach to compute the thermal conductivity of a nonpairwise additive water model at supercritical conditions, and of a liquid hydrogen system described by a machine-learning interatomic potential, at 33 GPa and 2000 K.

Evidence for supercritical behaviour of high-pressure liquid hydrogen - Cheng, Bingqing; Mazzola, Guglielmo; Pickard, Chris J.; Ceriotti, Michele (Nature)
Hydrogen, the simplest and most abundant element in the Universe, develops a remarkably complex behaviour upon compression^1. Since Wigner predicted the dissociation and metallization of solid hydrogen at megabar pressures almost a century ago^2, several efforts have been made to explain the many unusual properties of dense hydrogen, including a rich and poorly understood solid polymorphism^1,3-5, an anomalous melting line6 and the possible transition to a superconducting state^7. Experiments at such extreme conditions are challenging and often lead to hard-to-interpret and controversial observations, whereas theoretical investigations are constrained by the huge computational cost of sufficiently accurate quantum mechanical calculations. Here we present a theoretical study of the phase diagram of dense hydrogen that uses machine learning to 'learn' potential-energy surfaces and interatomic forces from reference calculations and then predict them at low computational cost, overcoming length- and timescale limitations. We reproduce both the re-entrant melting behaviour and the polymorphism of the solid phase. Simulations using our machine-learning-based potentials provide evidence for a continuous molecular-to-atomic transition in the liquid, with no first-order transition observed above the melting line. This suggests a smooth transition between insulating and metallic layers in giant gas planets, and reconciles existing discrepancies between experiments as a manifestation of supercritical behaviour.

Snow depth patterns in a high mountain Andean catchment from satellite optical tristereoscopic remote sensing - Shaw, Thomas E.; Gascoin, Simon; Mendoza, Pablo A.; Pellicciotti, Francesca; McPhee, James (Water Resources Research)
Obtaining detailed information about high mountain snowpacks is often limited by insufficient ground-based observations and uncertainty in the (re)distribution of solid precipitation. We utilize high-resolution optical images from Pléiades satellites to generate a snow depth map, at a spatial resolution of 4 m, for a high mountain catchment of central Chile. Results are negatively biased (median difference of −0.22 m) when compared against observations from a terrestrial Light Detection And Ranging scan, though replicate general snow depth variability well. Additionally, the Pléiades dataset is subject to data gaps (17% of total pixels), negative values for shallow snow (12%), and noise on slopes >40–50° (2%). We correct and filter the Pléiades snow depths using surface classification techniques of snow-free areas and a random forest model for data gap filling. Snow depths (with an estimated error of ~0.36 m) average 1.66 m and relate well to topographical parameters such as elevation and northness in a similar way to previous studies. However, estimations of snow depth based upon topography (TOPO) or physically based modeling (DBSM) cannot resolve localized processes (i.e., avalanching or wind scouring) that are detected by Pléiades, even when forced with locally calibrated data. Comparing these alternative model approaches to corrected Pléiades snow depths reveals total snow volume differences between −28% (DBSM) and +54% (TOPO) for the catchment and large differences across most elevation bands. Pléiades represents an important contribution to understanding snow accumulation at sparsely monitored catchments, though ideally requires a careful systematic validation procedure to identify catchment-scale biases and errors in the snow depth derivation.
Keywords: Water Science and Technology

The utility of optical satellite winter snow depths for initializing a glacio‐hydrological model of a High‐Elevation, Andean catchment - Shaw, Thomas E.; Caro, Alexis; Mendoza, Pablo; Ayala, Álvaro; Pellicciotti, Francesca; Gascoin, Simon; McPhee, James (Water Resources Research)
Information about end-of-winter spatial distribution of snow depth is important for seasonal forecasts of spring/summer streamflow in high-mountain regions. Nevertheless, such information typically relies upon extrapolation from a sparse network of observations at low elevations. Here, we test the potential of high-resolution snow depth data derived from optical stereophotogrammetry of Pléiades satellites for improving the representation of snow depth initial conditions (SDICs) in a glacio-hydrological model and assess potential improvements in the skill of snowmelt and streamflow simulations in a high-elevation Andean catchment. We calibrate model parameters controlling glacier mass balance and snow cover evolution using ground-based and satellite observations, and consider the relative importance of accurate estimates of SDICs compared to model parameters and forcings. We find that Pléiades SDICs improve the simulation of snow-covered area, glacier mass balance, and monthly streamflow compared to alternative SDICs based upon extrapolation of meteorological variables or statistical methods to estimate SDICs based upon topography. Model simulations are found to be sensitive to SDICs in the early spring (up to 48% variability in modeled streamflow compared to the best estimate model), and to temperature gradients in all months that control albedo and melt rates over a large elevation range (>2,400 m). As such, appropriately characterizing the distribution of total snow volume with elevation is important for reproducing total streamflow and the proportions of snowmelt. Therefore, optical stereo-photogrammetry offers an advantage for obtaining SDICs that aid both the timing and magnitude of streamflow simulations, process representation (e.g., snow cover evolution) and has the potential for large spatial domains.
Keywords: Water Science and Technology

Glacier runoff variations since 1955 in the Maipo River basin, in the semiarid Andes of central Chile - Ayala, Álvaro; Farías-Barahona, David; Huss, Matthias; Pellicciotti, Francesca; McPhee, James; Farinotti, Daniel (The Cryosphere)
As glaciers adjust their size in response to climate variations, long-term changes in meltwater production can be expected, affecting the local availability of water resources. We investigate glacier runoff in the period 1955–2016 in the Maipo River basin (4843 km2, 33.0–34.3∘ S, 69.8–70.5∘ W), in the semiarid Andes of Chile. The basin contains more than 800 glaciers, which cover 378 km2 in total (inventoried in 2000). We model the mass balance and runoff contribution of 26 glaciers with the physically oriented and fully distributed TOPKAPI (Topographic Kinematic Approximation and Integration)-ETH glacio-hydrological model and extrapolate the results to the entire basin. TOPKAPI-ETH is run at a daily time step using several glaciological and meteorological datasets, and its results are evaluated against streamflow records, remotely sensed snow cover, and geodetic mass balances for the periods 1955–2000 and 2000–2013. Results show that in 1955–2016 glacier mass balance had a general decreasing trend as a basin average but also had differences between the main sub-catchments. Glacier volume decreased by one-fifth (from 18.6±4.5 to 14.9±2.9 km3). Runoff from the initially glacierized areas was 177±25 mm yr−1 (16±7 % of the total contributions to the basin), but it shows a decreasing sequence of maxima, which can be linked to the interplay between a decrease in precipitation since the 1980s and the reduction of ice melt. Glaciers in the Maipo River basin will continue retreating because they are not in equilibrium with the current climate. In a hypothetical constant climate scenario, glacier volume would reduce to 81±38 % of the year 2000 volume, and glacier runoff would be 78±30 % of the 1955–2016 average. This would considerably decrease the drought mitigation capacity of the basin.
Keywords: Earth-Surface Processes; Water Science and Technology

Modelling spatial patterns of near-surface air temperature over a decade of melt seasons on McCall Glacier, Alaska - Troxler, Patrick; Ayala, Álvaro; Shaw, Thomas E.; Nolan, Matt; Brock, Ben W.; Pellicciotti, Francesca (Journal of Glaciology)
We examine the spatial patterns of near-surface air temperature (Ta) over a melting glacier using a multi-annual dataset from McCall Glacier, Alaska. The dataset consists of a 10-year (2005–2014) meteorological record along the glacier centreline up to an upper glacier cirque, spanning an elevation difference of 900 m. We test the validity of on-glacier linear lapse rates, and a model that calculates Ta based on the influence of katabatic winds and other heat sources along the glacier flow line. During the coldest hours of each summer (10% of time), average lapse rates across the entire glacier range from −4.7 to −6.7°C km−1, with a strong relationship between Ta and elevation (R2 > 0.7). During warm conditions, Ta shows more complex, non-linear patterns that are better explained by the flow line-dependent model, reducing errors by up to 0.5°C compared with linear lapse rates, although more uncertainty might be associated with these observations due to occasionally poor sensor ventilation. We conclude that Ta spatial distribution can vary significantly from year to year, and from one glacier section to another. Importantly, extrapolations using linear lapse rates from the ablation zone might lead to large underestimations of Ta on the upper glacier areas.
Keywords: Earth-Surface Processes

Seasonal dynamics of a temperate Tibetan glacier revealed by high-resolution UAV photogrammetry and in situ measurements - Yang, Wei; Zhao, Chuanxi; Westoby, Matthew; Yao, Tandong; Wang, Yongjie; Pellicciotti, Francesca; Zhou, Jianmin; He, Zhen; Miles, Evan (Remote Sensing)
The seasonal dynamic changes of Tibetan glaciers have seen little prior investigation, despite the increase in geodetic studies of multi-year changes. This study compares seasonal glacier dynamics (“cold” and “warm” seasons) in the ablation zone of Parlung No. 4 Glacier, a temperate glacier in the monsoon-influenced southeastern Tibetan Plateau, by using repeat unpiloted aerial vehicle (UAV) surveys combined with Structure-from-Motion (SfM) photogrammetry and ground stake measurements. Our results showed that the surveyed ablation zone had a mean change of −2.7 m of ice surface elevation during the period of September 2018 to October 2019 but is characterized by significant seasonal cyclic variations with ice surface elevation lifting (+2.0 m) in the cold season (September 2018 to June 2019) but lowering (−4.7 m) in the warm season (June 2019 to October 2019). Over an annual timescale, surface lowering was greatly suppressed by the resupply of ice from the glacier’s accumulation area—the annual emergence velocity compensates for about 55% of surface ablation in our study area. Cold season emergence velocities (3.0 ± 1.2 m) were ~5-times larger than those observed in the warm season (0.6 ± 1.0 m). Distinct spring precipitation patterns may contribute to these distinct seasonal signals. Such seasonal dynamic conditions are possibly critical for different glacier responses to climate change in this region of the Tibetan Plateau, and perhaps further afield.

Learning representations for binary-classification without backpropagation - Lechner, Mathias (8th International Conference on Learning Representations)
The family of feedback alignment (FA) algorithms aims to provide a more biologically motivated alternative to backpropagation (BP), by substituting the computations that are unrealistic to be implemented in physical brains. While FA algorithms have been shown to work well in practice, there is a lack of rigorous theory proofing their learning capabilities. Here we introduce the first feedback alignment algorithm with provable learning guarantees. In contrast to existing work, we do not require any assumption about the size or depth of the network except that it has a single output neuron, i.e., such as for binary classification tasks. We show that our FA algorithm can deliver its theoretical promises in practice, surpassing the learning performance of existing FA methods and matching backpropagation in binary classification tasks. Finally, we demonstrate the limits of our FA variant when the number of output neurons grows beyond a certain quantity.

Unsupervised object-centric video generation and decomposition in 3D - Henderson, Paul M; Lampert, Christoph (34th Conference on Neural Information Processing Systems)
A natural approach to generative modeling of videos is to represent them as a composition of moving objects. Recent works model a set of 2D sprites over a slowly-varying background, but without considering the underlying 3D scene that gives rise to them. We instead propose to model a video as the view seen while moving through a scene with multiple 3D objects and a 3D background. Our model is trained from monocular videos without any supervision, yet learns to generate coherent 3D scenes containing several moving objects. We conduct detailed experiments on two datasets, going beyond the visual complexity supported by state-of-the-art generative approaches. We evaluate our method on depth-prediction and 3D object detection---tasks which cannot be addressed by those earlier works---and show it out-performs them even on 2D instance segmentation and tracking.

The Arabidopsis epigenetic regulator ICU11 as an accessory protein of polycomb repressive complex 2 - Bloomer, Rebecca H.; Hutchison, Claire E.; Bäurle, Isabel; Walker, James; Fang, Xiaofeng; Perera, Pumi; Velanis, Christos N.; Gümüs, Serin; Spanos, Christos; Rappsilber, Juri; Feng, Xiaoqi; Goodrich, Justin; et al. (Proceedings of the National Academy of Sciences)
Molecular mechanisms enabling the switching and maintenance of epigenetic states are not fully understood. Distinct histone modifications are often associated with ON/OFF epigenetic states, but how these states are stably maintained through DNA replication, yet in certain situations switch from one to another remains unclear. Here, we address this problem through identification of Arabidopsis INCURVATA11 (ICU11) as a Polycomb Repressive Complex 2 accessory protein. ICU11 robustly immunoprecipitated in vivo with PRC2 core components and the accessory proteins, EMBRYONIC FLOWER 1 (EMF1), LIKE HETEROCHROMATIN PROTEIN1 (LHP1), and TELOMERE_REPEAT_BINDING FACTORS (TRBs). ICU11 encodes a 2-oxoglutarate-dependent dioxygenase, an activity associated with histone demethylation in other organisms, and mutant plants show defects in multiple aspects of the Arabidopsis epigenome. To investigate its primary molecular function we identified the Arabidopsis FLOWERING LOCUS C (FLC) as a direct target and found icu11 disrupted the cold-induced, Polycomb-mediated silencing underlying vernalization. icu11 prevented reduction in H3K36me3 levels normally seen during the early cold phase, supporting a role for ICU11 in H3K36me3 demethylation. This was coincident with an attenuation of H3K27me3 at the internal nucleation site in FLC, and reduction in H3K27me3 levels across the body of the gene after plants were returned to the warm. Thus, ICU11 is required for the cold-induced epigenetic switching between the mutually exclusive chromatin states at FLC, from the active H3K36me3 state to the silenced H3K27me3 state. These data support the importance of physical coupling of histone modification activities to promote epigenetic switching between opposing chromatin states.
Keywords: Multidisciplinary

AXR1 affects DNA methylation independently of its role in regulating meiotic crossover localization - Christophorou, Nicolas; She, Wenjing; Long, Jincheng; Hurel, Aurélie; Beaubiat, Sébastien; Idir, Yassir; Tagliaro-Jahns, Marina; Chambon, Aurélie; Solier, Victor; Vezon, Daniel; Grelon, Mathilde; Feng, Xiaoqi; et al. (PLOS Genetics)
Meiotic crossovers (COs) are important for reshuffling genetic information between homologous chromosomes and they are essential for their correct segregation. COs are unevenly distributed along chromosomes and the underlying mechanisms controlling CO localization are not well understood. We previously showed that meiotic COs are mis-localized in the absence of AXR1, an enzyme involved in the neddylation/rubylation protein modification pathway in Arabidopsis thaliana. Here, we report that in axr1-/-, male meiocytes show a strong defect in chromosome pairing whereas the formation of the telomere bouquet is not affected. COs are also redistributed towards subtelomeric chromosomal ends where they frequently form clusters, in contrast to large central regions depleted in recombination. The CO suppressed regions correlate with DNA hypermethylation of transposable elements (TEs) in the CHH context in axr1-/- meiocytes. Through examining somatic methylomes, we found axr1-/- affects DNA methylation in a plant, causing hypermethylation in all sequence contexts (CG, CHG and CHH) in TEs. Impairment of the main pathways involved in DNA methylation is epistatic over axr1-/- for DNA methylation in somatic cells but does not restore regular chromosome segregation during meiosis. Collectively, our findings reveal that the neddylation pathway not only regulates hormonal perception and CO distribution but is also, directly or indirectly, a major limiting pathway of TE DNA methylation in somatic cells.
Keywords: Cancer Research; Genetics (clinical); Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

Primitive divisors of sequences associated to elliptic curves - Verzobio, Matteo (Journal of Number Theory)
Let be a sequence of points on an elliptic curve defined over a number field K. In this paper, we study the denominators of the x-coordinates of this sequence. We prove that, if Q is a torsion point of prime order, then for n large enough there always exists a primitive divisor. Later on, we show the link between the study of the primitive divisors and a Lang-Trotter conjecture. Indeed, given two points P and Q on the elliptic curve, we prove a lower bound for the number of primes p such that P is in the orbit of Q modulo p.
Keywords: Algebra and Number Theory

Extracting ice phases from liquid water: Why a machine-learning water model generalizes so well - Monserrat, Bartomeu; Brandenburg, Jan Gerit; Engel, Edgar A.; Cheng, Bingqing (arXiv)
We investigate the structural similarities between liquid water and 53 ices, including 20 known crystalline phases. We base such similarity comparison on the local environments that consist of atoms within a certain cutoff radius of a central atom. We reveal that liquid water explores the local environments of the diverse ice phases, by directly comparing the environments in these phases using general atomic descriptors, and also by demonstrating that a machine-learning potential trained on liquid water alone can predict the densities, the lattice energies, and vibrational properties of the ices. The finding that the local environments characterising the different ice phases are found in water sheds light on water phase behaviors, and rationalizes the transferability of water models between different phases.

A 3-in-1 hand-held ambient mass spectrometry interface for identification and 2D localization of chemicals on surfaces - Meisenbichler, Christina; Kluibenschedl, Florian; Müller, Thomas (Analytical Chemistry)
Desorption electrospray ionization (DESI), easy ambient sonic-spray ionization (EASI) and low-temperature plasma (LTP) ionization are powerful ambient ionization techniques for mass spectrometry. However, every single method has its limitation in terms of polarity and molecular weight of analyte molecules. After the miniaturization of every possible component of the different ion sources, we finally were able to embed two emitters and an ion transfer tubing into a small, hand-held device. The pen-like interface is connected to the mass spectrometer and a separate control unit via a bundle of flexible tubing and cables. The novel device allows the user to ionize an extended range of chemicals by simple switching between DESI, voltage-free EASI, or LTP ionization as well as to freely move the interface over a surface of interest. A mini camera, which is mounted on the tip of the pen, magnifies the desorption area and enables a simple positioning of the pen. The interface was successfully tested using different types of chemicals, pharmaceuticals, and real life samples. Moreover, the combination of optical data from the camera module and chemical data obtained by mass analysis facilitates a novel type of imaging mass spectrometry, which we name “interactive mass spectrometry imaging (IMSI)”.
Keywords: Analytical Chemistry

Phylloxanthobilins are abundant linear tetrapyrroles from chlorophyll breakdown with activities against cancer cells - Karg, Cornelia A.; Wang, Pengyu; Kluibenschedl, Florian; Müller, Thomas; Allmendinger, Lars; Vollmar, Angelika M.; Moser, Simone (European Journal of Organic Chemistry)
Linear tetrapyrroles, called phyllobilins, are obtained as major catabolites upon chlorophyll degradation. Primarily, colorless phylloleucobilins featuring four deconjugated pyrrole units were identified. Their yellow counterparts, phylloxanthobilins, were discovered more recently. Although the two catabolites differ only by one double bond, physicochemical properties are very distinct. Moreover, the presence of the double bond seems to enhance physiologically relevant bioactivities: in contrast to phylloleucobilin, we identified a potent anti-proliferative activity for a phylloxanthobilin, and show that this natural product induces apoptotic cell death and a cell cycle arrest in cancer cells. Interestingly, upon modifying inactive phylloleucobilin by esterification, an anti-proliferative activity can be observed that increases with the chain lengths of the alkyl esters. We provide first evidence for anti-cancer activity of phyllobilins, report a novel plant source for a phylloxanthobilin, and by using paper spray MS, show that these bioactive yellow chlorophyll catabolites are more prevalent in Nature than previously assumed.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Austrian High-Performance-Computing meeting (AHPC2020)
This booklet is a collection of abstracts presented at the AHPC conference.

How many bits does it take to quantize your neural network? - Giacobbe, Mirco; Henzinger, Thomas A; Lechner, Mathias (International Conference on Tools and Algorithms for the Construction and Analysis of Systems)
Quantization converts neural networks into low-bit fixed-point computations which can be carried out by efficient integer-only hardware, and is standard practice for the deployment of neural networks on real-time embedded devices. However, like their real-numbered counterpart, quantized networks are not immune to malicious misclassification caused by adversarial attacks. We investigate how quantization affects a network’s robustness to adversarial attacks, which is a formal verification question. We show that neither robustness nor non-robustness are monotonic with changing the number of bits for the representation and, also, neither are preserved by quantization from a real-numbered network. For this reason, we introduce a verification method for quantized neural networks which, using SMT solving over bit-vectors, accounts for their exact, bit-precise semantics. We built a tool and analyzed the effect of quantization on a classifier for the MNIST dataset. We demonstrate that, compared to our method, existing methods for the analysis of real-numbered networks often derive false conclusions about their quantizations, both when determining robustness and when detecting attacks, and that existing methods for quantized networks often miss attacks. Furthermore, we applied our method beyond robustness, showing how the number of bits in quantization enlarges the gender bias of a predictor for students’ grades.

The topological correctness of PL-approximations of isomanifolds - Boissonnat, Jean-Daniel; Wintraecken, Mathijs (36th International Symposium on Computational Geometry)
Isomanifolds are the generalization of isosurfaces to arbitrary dimension and codimension, i.e. manifolds defined as the zero set of some multivariate vector-valued smooth function f: ℝ^d → ℝ^(d-n). A natural (and efficient) way to approximate an isomanifold is to consider its Piecewise-Linear (PL) approximation based on a triangulation 𝒯 of the ambient space ℝ^d. In this paper, we give conditions under which the PL-approximation of an isomanifold is topologically equivalent to the isomanifold. The conditions are easy to satisfy in the sense that they can always be met by taking a sufficiently fine triangulation 𝒯. This contrasts with previous results on the triangulation of manifolds where, in arbitrary dimensions, delicate perturbations are needed to guarantee topological correctness, which leads to strong limitations in practice. We further give a bound on the Fréchet distance between the original isomanifold and its PL-approximation. Finally we show analogous results for the PL-approximation of an isomanifold with boundary.

SQUID-on-tip with single-electron spin sensitivity for high-field and ultra-low temperature nanomagnetic imaging - Anahory, Y.; Naren, H. R.; Lachman, E. O.; Sinai, S. Buhbut; Uri, A.; Embon, L.; Yaakobi, E.; Myasoedov, Y.; Huber, M. E.; Klajn, Rafal; Zeldov, E. (Nanoscale)
Scanning nanoscale superconducting quantum interference devices (nanoSQUIDs) are of growing interest for highly sensitive quantitative imaging of magnetic, spintronic, and transport properties of low-dimensional systems. Utilizing specifically designed grooved quartz capillaries pulled into a sharp pipette, we have fabricated the smallest SQUID-on-tip (SOT) devices with effective diameters down to 39 nm. Integration of a resistive shunt in close proximity to the pipette apex combined with self-aligned deposition of In and Sn, have resulted in SOT with a flux noise of 42 n$Φ_0$Hz$^{-1/2}$, yielding a record low spin noise of 0.29 $μ_B$Hz$^{-1/2}$. In addition, the new SOTs function at sub-Kelvin temperatures and in high magnetic fields of over 2.5 T. Integrating the SOTs into a scanning probe microscope allowed us to image the stray field of a single Fe$_3$O$_4$ nanocube at 300 mK. Our results show that the easy magnetization axis direction undergoes a transition from the (111) direction at room temperature to an in-plane orientation, which could be attributed to the Verwey phase transition in Fe$_3$O$_4$.

Connectivity of triangulation flip graphs in the plane (Part II: Bistellar flips) - Wagner, Uli; Welzl, Emo (36th International Symposium on Computational Geometry)
Given a finite point set P in general position in the plane, a full triangulation is a maximal straight-line embedded plane graph on P. A partial triangulation on P is a full triangulation of some subset P' of P containing all extreme points in P. A bistellar flip on a partial triangulation either flips an edge, removes a non-extreme point of degree 3, or adds a point in P ⧵ P' as vertex of degree 3. The bistellar flip graph has all partial triangulations as vertices, and a pair of partial triangulations is adjacent if they can be obtained from one another by a bistellar flip. The goal of this paper is to investigate the structure of this graph, with emphasis on its connectivity. For sets P of n points in general position, we show that the bistellar flip graph is (n-3)-connected, thereby answering, for sets in general position, an open questions raised in a book (by De Loera, Rambau, and Santos) and a survey (by Lee and Santos) on triangulations. This matches the situation for the subfamily of regular triangulations (i.e., partial triangulations obtained by lifting the points and projecting the lower convex hull), where (n-3)-connectivity has been known since the late 1980s through the secondary polytope (Gelfand, Kapranov, Zelevinsky) and Balinski’s Theorem. Our methods also yield the following results (see the full version [Wagner and Welzl, 2020]): (i) The bistellar flip graph can be covered by graphs of polytopes of dimension n-3 (products of secondary polytopes). (ii) A partial triangulation is regular, if it has distance n-3 in the Hasse diagram of the partial order of partial subdivisions from the trivial subdivision. (iii) All partial triangulations are regular iff the trivial subdivision has height n-3 in the partial order of partial subdivisions. (iv) There are arbitrarily large sets P with non-regular partial triangulations, while every proper subset has only regular triangulations, i.e., there are no small certificates for the existence of non-regular partial triangulations (answering a question by F. Santos in the unexpected direction).

Connectivity of triangulation flip graphs in the plane (Part I: Edge flips) - Wagner, Uli; Welzl, Emo (Proceedings of the Annual ACM-SIAM Symposium on Discrete Algorithms)
In a straight-line embedded triangulation of a point set P in the plane, removing an inner edge and—provided the resulting quadrilateral is convex—adding the other diagonal is called an edge flip. The (edge) flip graph has all triangulations as vertices, and a pair of triangulations is adjacent if they can be obtained from each other by an edge flip. The goal of this paper is to contribute to a better understanding of the flip graph, with an emphasis on its connectivity. For sets in general position, it is known that every triangulation allows at least edge flips (a tight bound) which gives the minimum degree of any flip graph for n points. We show that for every point set P in general position, the flip graph is at least -vertex connected. Somewhat more strongly, we show that the vertex connectivity equals the minimum degree occurring in the flip graph, i.e. the minimum number of flippable edges in any triangulation of P, provided P is large enough. Finally, we exhibit some of the geometry of the flip graph by showing that the flip graph can be covered by 1-skeletons of polytopes of dimension (products of associahedra). A corresponding result ((n – 3)-vertex connectedness) can be shown for the bistellar flip graph of partial triangulations, i.e. the set of all triangulations of subsets of P which contain all extreme points of P. This will be treated separately in a second part.

How do species barriers decay? concordance and local introgression in mosaic hybrid zones of mussels - Simon, Alexis; Fraisse, Christelle; El Ayari, Tahani; Liautard-Haag, Cathy; Strelkov, Petr; Welch, John; Bierne, Nicolas
The Mytilus complex of marine mussel species forms a mosaic of hybrid zones, found across temperate regions of the globe. This allows us to study "replicated" instances of secondary contact between closely-related species. Previous work on this complex has shown that local introgression is both widespread and highly heterogeneous, and has identified SNPs that are outliers of differentiation between lineages. Here, we developed an ancestry-informative panel of such SNPs. We then compared their frequencies in newly-sampled populations, including samples from within the hybrid zones, and parental populations at different distances from the contact. Results show that close to the hybrid zones, some outlier loci are near to fixation for the heterospecific allele, suggesting enhanced local introgression, or the local sweep of a shared ancestral allele. Conversely, genomic cline analyses, treating local parental populations as the reference, reveal a globally high concordance among loci, albeit with a few signals of asymmetric introgression. Enhanced local introgression at specific loci is consistent with the early transfer of adaptive variants after contact, possibly including asymmetric bi-stable variants (Dobzhansky-Muller incompatibilities), or haplotypes loaded with fewer deleterious mutations. Having escaped one barrier, however, these variants can be trapped or delayed at the next barrier, confining the introgression locally. These results shed light on the decay of species barriers during phases of contact.

VCF files of synonymous SNPs related to: Genomic inference of complex domestication histories in three Solanaceae species - Arnoux, Stephanie; Fraisse, Christelle; Sauvage, Christopher
Domestication is a human-induced selection process that imprints the genomes of domesticated populations over a short evolutionary time scale, and that occurs in a given demographic context. Reconstructing historical gene flow, effective population size changes and their timing is therefore of fundamental interest to understand how plant demography and human selection jointly shape genomic divergence during domestication. Yet, the comparison under a single statistical framework of independent domestication histories across different crop species has been little evaluated so far. Thus, it is unclear whether domestication leads to convergent demographic changes that similarly affect crop genomes. To address this question, we used existing and new transcriptome data on three crop species of Solanaceae (eggplant, pepper and tomato), together with their close wild relatives. We fitted twelve demographic models of increasing complexity on the unfolded joint allele frequency spectrum for each wild/crop pair, and we found evidence for both shared and species-specific demographic processes between species. A convergent history of domestication with gene-flow was inferred for all three species, along with evidence of strong reduction in the effective population size during the cultivation stage of tomato and pepper. The absence of any reduction in size of the crop in eggplant stands out from the classical view of the domestication process; as does the existence of a “protracted period” of management before cultivation. Our results also suggest divergent management strategies of modern cultivars among species as their current demography substantially differs. Finally, the timing of domestication is species-specific and supported by the few historical records available.

Molecular photoswitching in confined spaces - Grommet, Angela B.; Lee, Lucia M.; Klajn, Rafal (Accounts of Chemical Research)
In nature, light is harvested by photoactive proteins to drive a range of biological processes, including photosynthesis, phototaxis, vision, and ultimately life. Bacteriorhodopsin, for example, is a protein embedded within archaeal cell membranes that binds the chromophore retinal within its hydrophobic pocket. Exposure to light triggers regioselective photoisomerization of the confined retinal, which in turn initiates a cascade of conformational changes within the protein, triggering proton flux against the concentration gradient, providing the microorganisms with the energy to live. We are inspired by these functions in nature to harness light energy using synthetic photoswitches under confinement. Like retinal, synthetic photoswitches require some degree of conformational flexibility to isomerize. In nature, the conformational change associated with retinal isomerization is accommodated by the structural flexibility of the opsin host, yet it results in steric communication between the chromophore and the protein. Similarly, we strive to design systems wherein isomerization of confined photoswitches results in steric communication between a photoswitch and its confining environment. To achieve this aim, a balance must be struck between molecular crowding and conformational freedom under confinement: too much crowding prevents switching, whereas too much freedom resembles switching of isolated molecules in solution, preventing communication. In this Account, we discuss five classes of synthetic light-switchable compounds—diarylethenes, anthracenes, azobenzenes, spiropyrans, and donor–acceptor Stenhouse adducts—comparing their behaviors under confinement and in solution. The environments employed to confine these photoswitches are diverse, ranging from planar surfaces to nanosized cavities within coordination cages, nanoporous frameworks, and nanoparticle aggregates. The trends that emerge are primarily dependent on the nature of the photoswitch and not on the material used for confinement. In general, we find that photoswitches requiring less conformational freedom for switching are, as expected, more straightforward to isomerize reversibly under confinement. Because these compounds undergo only small structural changes upon isomerization, however, switching does not propagate into communication with their environment. Conversely, photoswitches that require more conformational freedom are more challenging to switch under confinement but also can influence system-wide behavior. Although we are primarily interested in the effects of geometric constraints on photoswitching under confinement, additional effects inevitably emerge when a compound is removed from solution and placed within a new, more crowded environment. For instance, we have found that compounds that convert to zwitterionic isomers upon light irradiation often experience stabilization of these forms under confinement. This effect results from the mutual stabilization of zwitterions that are brought into close proximity on surfaces or within cavities. Furthermore, photoswitches can experience preorganization under confinement, influencing the selectivity and efficiency of their photoreactions. Because intermolecular interactions arising from confinement cannot be considered independently from the effects of geometric constraints, we describe all confinement effects concurrently throughout this Account.
Keywords: General Medicine; General Chemistry

Modulating the optical properties of BODIPY dyes by noncovalent dimerization within a flexible coordination cage - Gemen, Julius; Ahrens, Johannes; Shimon, Linda J. W.; Klajn, Rafal (Journal of the American Chemical Society)
Aggregation of organic molecules can drastically affect their physicochemical properties. For instance, the optical properties of BODIPY dyes are inherently related to the degree of aggregation and the mutual orientation of BODIPY units within these aggregates. Whereas the noncovalent aggregation of various BODIPY dyes has been studied in diverse media, the ill-defined nature of these aggregates has made it difficult to elucidate the structure–property relationships. Here, we studied the encapsulation of three structurally simple BODIPY derivatives within the hydrophobic cavity of a water-soluble, flexible PdII6L4 coordination cage. The cavity size allowed for the selective encapsulation of two dye molecules, irrespective of the substitution pattern on the BODIPY core. Working with a model, a pentamethyl-substituted derivative, we found that the mutual orientation of two BODIPY units in the cage’s cavity was remarkably similar to that in the crystalline state of the free dye, allowing us to isolate and characterize the smallest possible noncovalent H-type BODIPY aggregate, namely, an H-dimer. Interestingly, a CF3-substituted BODIPY, known for forming J-type aggregates, was also encapsulated as an H-dimer. Taking advantage of the dynamic nature of encapsulation, we developed a system in which reversible switching between H- and J-aggregates can be induced for multiple cycles simply by addition and subsequent destruction of the cage. We expect that the ability to rapidly and reversibly manipulate the optical properties of supramolecular inclusion complexes in aqueous media will open up avenues for developing detection systems that operate within biological environments.
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Improving fatigue resistance of dihydropyrene by encapsulation within a coordination cage - Canton, Martina; Grommet, Angela B.; Pesce, Luca; Gemen, Julius; Li, Shiming; Diskin-Posner, Yael; Credi, Alberto; Pavan, Giovanni M.; Andréasson, Joakim; Klajn, Rafal (Journal of the American Chemical Society)
Photochromic molecules undergo reversible isomerization upon irradiation with light at different wavelengths, a process that can alter their physical and chemical properties. For instance, dihydropyrene (DHP) is a deep-colored compound that isomerizes to light-brown cyclophanediene (CPD) upon irradiation with visible light. CPD can then isomerize back to DHP upon irradiation with UV light or thermally in the dark. Conversion between DHP and CPD is thought to proceed via a biradical intermediate; bimolecular events involving this unstable intermediate thus result in rapid decomposition and poor cycling performance. Here, we show that the reversible isomerization of DHP can be stabilized upon confinement within a PdII6L4 coordination cage. By protecting this reactive intermediate using the cage, each isomerization reaction proceeds to higher yield, which significantly decreases the fatigue experienced by the system upon repeated photocycling. Although molecular confinement is known to help stabilize reactive species, this effect is not typically employed to protect reactive intermediates and thus improve reaction yields. We envisage that performing reactions under confinement will not only improve the cyclic performance of photochromic molecules, but may also increase the amount of product obtainable from traditionally low-yielding organic reactions.
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Molecular factors controlling the isomerization of Azobenzenes in the cavity of a flexible coordination cage - Pesce, Luca; Perego, Claudio; Grommet, Angela B.; Klajn, Rafal; Pavan, Giovanni M. (Journal of the American Chemical Society)
Photoswitchable molecules are employed for many applications, from the development of active materials to the design of stimuli-responsive molecular systems and light-powered molecular machines. To fully exploit their potential, we must learn ways to control the mechanism and kinetics of their photoinduced isomerization. One possible strategy involves confinement of photoresponsive switches such as azobenzenes or spiropyrans within crowded molecular environments, which may allow control over their light-induced conversion. However, the molecular factors that influence and control the switching process under realistic conditions and within dynamic molecular regimes often remain difficult to ascertain. As a case study, here we have employed molecular models to probe the isomerization of azobenzene guests within a Pd(II)-based coordination cage host in water. Atomistic molecular dynamics and metadynamics simulations allow us to characterize the flexibility of the cage in the solvent, the (rare) guest encapsulation and release events, and the relative probability/kinetics of light-induced isomerization of azobenzene analogues in these host–guest systems. In this way, we can reconstruct the mechanism of azobenzene switching inside the cage cavity and explore key molecular factors that may control this event. We obtain a molecular-level insight on the effects of crowding and host–guest interactions on azobenzene isomerization. The detailed picture elucidated by this study may enable the rational design of photoswitchable systems whose reactivity can be controlled via host–guest interactions.
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Light‐driven proton transfer for cyclic and temporal switching of enzymatic nanoreactors - Moreno, Silvia; Sharan, Priyanka; Engelke, Johanna; Gumz, Hannes; Boye, Susanne; Oertel, Ulrich; Wang, Peng; Banerjee, Susanta; Klajn, Rafal; Voit, Brigitte; Lederer, Albena; Appelhans, Dietmar (Small)
Temporal activation of biological processes by visible light and subsequent return to an inactive state in the absence of light is an essential characteristic of photoreceptor cells. Inspired by these phenomena, light-responsive materials are very attractive due to the high spatiotemporal control of light irradiation, with light being able to precisely orchestrate processes repeatedly over many cycles. Herein, it is reported that light-driven proton transfer triggered by a merocyanine-based photoacid can be used to modulate the permeability of pH-responsive polymersomes through cyclic, temporally controlled protonation and deprotonation of the polymersome membrane. The membranes can undergo repeated light-driven swelling–contraction cycles without losing functional effectiveness. When applied to enzyme loaded-nanoreactors, this membrane responsiveness is used for the reversible control of enzymatic reactions. This combination of the merocyanine-based photoacid and pH-switchable nanoreactors results in rapidly responding and versatile supramolecular systems successfully used to switch enzymatic reactions ON and OFF on demand.
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Simplified successive cancellation decoding of polar codes has sublinear latency - Mondelli, Marco; Hashemi, Seyyed Ali; Cioffi, John; Goldsmith, Andrea (IEEE International Symposium on Information Theory - Proceedings)
This work analyzes the latency of the simplified successive cancellation (SSC) decoding scheme for polar codes proposed by Alamdar-Yazdi and Kschischang. It is shown that, unlike conventional successive cancellation decoding, where latency is linear in the block length, the latency of SSC decoding is sublinear. More specifically, the latency of SSC decoding is O(N 1−1/µ ), where N is the block length and µ is the scaling exponent of the channel, which captures the speed of convergence of the rate to capacity. Numerical results demonstrate the tightness of the bound and show that most of the latency reduction arises from the parallel decoding of subcodes of rate 0 and 1.

The young massive SMC cluster NGC 330 seen by MUSE - Bodensteiner, J.; Sana, H.; Mahy, L.; Patrick, L. R.; de Koter, A.; de Mink, S. E.; Evans, C. J.; Götberg, Ylva Louise Linsdotter; Langer, N.; Lennon, D. J.; Schneider, F. R. N.; Tramper, F. (Astronomy & Astrophysics)
Context. A majority of massive stars are part of binary systems, a large fraction of which will inevitably interact during their lives. Binary-interaction products (BiPs), that is, stars affected by such interaction, are expected to be commonly present in stellar populations. BiPs are thus a crucial ingredient in the understanding of stellar evolution. Aims. We aim to identify and characterize a statistically significant sample of BiPs by studying clusters of 10 − 40 Myr, an age at which binary population models predict the abundance of BiPs to be highest. One example of such a cluster is NGC 330 in the Small Magellanic Cloud. Methods. Using MUSE WFM-AO observations of NGC 330, we resolved the dense cluster core for the first time and were able to extract spectra of its entire massive star population. We developed an automated spectral classification scheme based on the equivalent widths of spectral lines in the red part of the spectrum. Results. We characterize the massive star content of the core of NGC 330, which contains more than 200 B stars, 2 O stars, 6 A-type supergiants, and 11 red supergiants. We find a lower limit on the Be star fraction of 32 ± 3% in the whole sample. It increases to at least 46 ± 10% when we only consider stars brighter than V = 17 mag. We estimate an age of the cluster core between 35 and 40 Myr and a total cluster mass of 88−18+17 × 103 M⊙. Conclusions. We find that the population in the cluster core is different than the population in the outskirts: while the stellar content in the core appears to be older than the stars in the outskirts, the Be star fraction and the observed binary fraction are significantly higher. Furthermore, we detect several BiP candidates that will be subject of future studies.
Keywords: stars: massive / stars: emission-line / Be / binaries: spectroscopic / blue stragglers / Magellanic Clouds

Sensitivity of the lower edge of the pair-instability black hole mass gap to the treatment of time-dependent convection - Renzo, M; Farmer, R J; Justham, S; de Mink, S E; Götberg, Ylva Louise Linsdotter; Marchant, P (Monthly Notices of the Royal Astronomical Society)
Gravitational-wave detections are now probing the black hole (BH) mass distribution, including the predicted pair-instability mass gap. These data require robust quantitative predictions, which are challenging to obtain. The most massive BH progenitors experience episodic mass ejections on time-scales shorter than the convective turnover time-scale. This invalidates the steady-state assumption on which the classic mixing length theory relies. We compare the final BH masses computed with two different versions of the stellar evolutionary code MESA ⁠: (i) using the default implementation of Paxton et al. (2018) and (ii) solving an additional equation accounting for the time-scale for convective deceleration. In the second grid, where stronger convection develops during the pulses and carries part of the energy, we find weaker pulses. This leads to lower amounts of mass being ejected and thus higher final BH masses of up to ∼5M⊙ ⁠. The differences are much smaller for the progenitors that determine the maximum mass of BHs below the gap. This prediction is robust at MBH,max≃48M⊙ ⁠, at least within the idealized context of this study. This is an encouraging indication that current models are robust enough for comparison with the present-day gravitational-wave detections. However, the large differences between individual models emphasize the importance of improving the treatment of convection in stellar models, especially in the light of the data anticipated from the third generation of gravitational-wave detectors.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Contribution from stars stripped in binaries to cosmic reionization of hydrogen and helium - Götberg, Ylva Louise Linsdotter; de Mink, S. E.; McQuinn, M.; Zapartas, E.; Groh, J. H.; Norman, C. (Astronomy & Astrophysics)
Massive stars are often found in binary systems, and it has been argued that binary products boost the ionizing radiation of stellar populations. Accurate predictions for binary products are needed to understand and quantify their contribution to cosmic reionization. We investigate the contribution of stars stripped in binaries because (1) they are, arguably, the best-understood products of binary evolution, (2) we recently produced the first radiative transfer calculations for the atmospheres of these stripped stars that predict their ionizing spectra, and (3) they are very promising sources because they boost the ionizing emission of stellar populations at late times. This allows stellar feedback to clear the surroundings such that a higher fraction of their photons can escape and ionize the intergalactic medium. Combining our detailed predictions for the ionizing spectra with a simple cosmic reionization model, we estimate that stripped stars contributed tens of percent of the photons that caused cosmic reionization of hydrogen, depending on the assumed escape fractions. More importantly, stripped stars harden the ionizing emission. We estimate that the spectral index for the ionizing part of the spectrum can increase to −1 compared to ≲ − 2 for single stars. At high redshift, stripped stars and massive single stars combined dominate the He II-ionizing emission, but we expect that active galactic nuclei drive cosmic helium reionization. Further observational consequences we expect are (1) high ionization states for the intergalactic gas surrounding stellar systems, such as C IV and Si IV, and (2) additional heating of the intergalactic medium of up to a few thousand Kelvin. Quantifying these warrants the inclusion of accurate models for stripped stars and other binary products in full cosmological simulations.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Predictions for the hydrogen-free ejecta of pulsational pair-instability supernovae - Renzo, M.; Farmer, R.; Justham, S.; Götberg, Ylva Louise Linsdotter; de Mink, S. E.; Zapartas, E.; Marchant, P.; Smith, N. (Astronomy & Astrophysics)
Present and upcoming time-domain astronomy efforts, in part driven by gravitational-wave follow-up campaigns, will unveil a variety of rare explosive transients in the sky. Here, we focus on pulsational pair-instability evolution, which can result in signatures that are observable with electromagnetic and gravitational waves. We simulated grids of bare helium stars to characterize the resulting black hole (BH) masses together with the ejecta composition, velocity, and thermal state. We find that the stars do not react “elastically” to the thermonuclear ignition in the core: there is not a one-to-one correspondence between pair-instability driven ignition and mass ejections, which causes ambiguity as to what is an observable pulse. In agreement with previous studies, we find that for initial helium core masses of 37.5 M⊙ ≲ MHe, init ≲ 41 M⊙, corresponding to carbon-oxygen core masses 27.5 M⊙ ≲ MCO ≲ 30.1 M⊙, the explosions are not strong enough to affect the surface. With increasing initial helium core mass, they become progressively stronger causing first large radial expansion (41 M⊙ ≲ MHe, init ≲ 42 M⊙, corresponding to 30.1 M⊙ ≲ MCO ≲ 30.8 M⊙) and, finally, also mass ejection episodes (for MHe, init ≳ 42 M⊙, or MCO ≳ 30.8 M⊙). The lowest mass helium core to be fully disrupted in a pair-instability supernova is MHe, init ≃ 80 M⊙, corresponding to MCO ≃ 55 M⊙. Models with MHe, init ≳ 200 M⊙ (MCO ≳ 114 M⊙) reach the photodisintegration regime, resulting in BHs with masses of MBH ≳ 125 M⊙. Although this is currently considered unlikely, if BHs from these models form via (weak) explosions, the previously-ejected material might be hit by the blast wave and convert kinetic energy into observable electromagnetic radiation. We characterize the hydrogen-free circumstellar material from the pulsational pair-instability of helium cores by simply assuming that the ejecta maintain a constant velocity after ejection. We find that our models produce helium-rich ejecta with mass of 10−3 M⊙ ≲ MCSM ≲ 40 M⊙, the larger values corresponding to the more massive progenitor stars. These ejecta are typically launched at a few thousand km s−1 and reach distances of ∼1012 − 1015 cm before the core-collapse of the star. The delays between mass ejection events and the final collapse span a wide and mass-dependent range (from subhour to 104 years), and the shells ejected can also collide with each other, powering supernova impostor events before the final core-collapse. The range of properties we find suggests a possible connection with (some) type Ibn supernovae.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Delayed photons from binary evolution help reionize the universe - Secunda, Amy; Cen, Renyue; Kimm, Taysun; Götberg, Ylva Louise Linsdotter; de Mink, Selma E. (The Astrophysical Journal)
High-resolution numerical simulations including feedback and aimed at calculating the escape fraction (fesc) of hydrogen-ionizing photons often assume stellar radiation based on single-stellar population synthesis models. However, strong evidence suggests the binary fraction of massive stars is ≳70%. Moreover, simulations so far have yielded values of fesc falling only on the lower end of the ∼10%–20% range, the amount presumed necessary to reionize the universe. Analyzing a high-resolution (4 pc) cosmological radiation-hydrodynamic simulation, we study how fesc changes when we include two different products of binary stellar evolution—stars stripped of their hydrogen envelopes and massive blue stragglers. Both produce significant amounts of ionizing photons 10–200 Myr after each starburst. We find the relative importance of these photons to be amplified with respect to escaped ionizing photons, because peaks in star formation rates (SFRs) and fesc are often out of phase by this 10–200 Myr. Additionally, low-mass, bursty galaxies emit Lyman continuum radiation primarily from binary products when SFRs are low. Observations of these galaxies by the James Webb Space Telescope could provide crucial information on the evolution of binary stars as a function of redshift. Overall, including stripped stars and massive blue stragglers increases our photon-weighted mean escape fraction ($\langle {f}_{esc}\rangle $) by ∼13% and ∼10%, respectively, resulting in $\langle {f}_{esc}\rangle =17 % $. Our results emphasize that using updated stellar population synthesis models with binary stellar evolution provides a more sound physical basis for stellar reionization.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The expansion of stripped-envelope stars: Consequences for supernovae and gravitational-wave progenitors - Laplace, E.; Götberg, Ylva Louise Linsdotter; de Mink, S. E.; Justham, S.; Farmer, R. (Astronomy & Astrophysics)
Massive binaries that merge as compact objects are the progenitors of gravitational-wave sources. Most of these binaries experience one or more phases of mass transfer, during which one of the stars loses all or part of its outer envelope and becomes a stripped-envelope star. The evolution of the size of these stripped stars is crucial in determining whether they experience further interactions and understanding their ultimate fate. We present new calculations of stripped-envelope stars based on binary evolution models computed with MESA. We use these to investigate their radius evolution as a function of mass and metallicity. We further discuss their pre-supernova observable characteristics and potential consequences of their evolution on the properties of supernovae from stripped stars. At high metallicity, we find that practically all of the hydrogen-rich envelope is removed, which is in agreement with earlier findings. Only progenitors with initial masses below 10 M⊙ expand to large radii (up to 100 R⊙), while more massive progenitors remain compact. At low metallicity, a substantial amount of hydrogen remains and the progenitors can, in principle, expand to giant sizes (> 400 R⊙) for all masses we consider. This implies that they can fill their Roche lobe anew. We show that the prescriptions commonly used in population synthesis models underestimate the stellar radii by up to two orders of magnitude. We expect that this has consequences for the predictions for gravitational-wave sources from double neutron star mergers, particularly with regard to their metallicity dependence.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Eliminating higher-multiplicity intersections, III. Codimension 2 - Avvakumov, Sergey; Wagner, Uli; Mabillard, Isaac; Skopenkov, A. B. (Russian Mathematical Surveys)

Non-commutative calculus, optimal transport and functional inequalities in dissipative quantum systems - Carlen, Eric A.; Maas, Jan (Journal of Statistical Physics)
We study dynamical optimal transport metrics between density matricesassociated to symmetric Dirichlet forms on finite-dimensional C∗-algebras. Our settingcovers arbitrary skew-derivations and it provides a unified framework that simultaneously generalizes recently constructed transport metrics for Markov chains, Lindblad equations, and the Fermi Ornstein–Uhlenbeck semigroup. We develop a non-nommutative differential calculus that allows us to obtain non-commutative Ricci curvature bounds, logarithmic Sobolev inequalities, transport-entropy inequalities, andspectral gap estimates.

Gromov's waist of non-radial Gaussian measures and radial non-Gaussian measures - Akopyan, Arseniy; Karasev, Roman (Geometric Aspects of Functional Analysis)
We study the Gromov waist in the sense of t-neighborhoods for measures in the Euclidean space, motivated by the famous theorem of Gromov about the waist of radially symmetric Gaussian measures. In particular, it turns our possible to extend Gromov’s original result to the case of not necessarily radially symmetric Gaussian measure. We also provide examples of measures having no t-neighborhood waist property, including a rather wide class of compactly supported radially symmetric measures and their maps into the Euclidean space of dimension at least 2. We use a simpler form of Gromov’s pancake argument to produce some estimates of t-neighborhoods of (weighted) volume-critical submanifolds in the spirit of the waist theorems, including neighborhoods of algebraic manifolds in the complex projective space. In the appendix of this paper we provide for reader’s convenience a more detailed explanation of the Caffarelli theorem that we use to handle not necessarily radially symmetric Gaussian measures.

A geometric version of the circle method - Browning, Timothy D; Sawin, Will (Annals of Mathematics)
We develop a geometric version of the circle method and use it to compute the compactly supported cohomology of the space of rational curves through a point on a smooth affine hypersurface of sufficiently low degree.

Optimal upper bound for the correlation energy of a Fermi gas in the mean-field regime - Benedikter, Niels P; Nam, Phan Thành; Porta, Marcello; Schlein, Benjamin; Seiringer, Robert (Communications in Mathematical Physics)
While Hartree–Fock theory is well established as a fundamental approximation for interacting fermions, it has been unclear how to describe corrections to it due to many-body correlations. In this paper we start from the Hartree–Fock state given by plane waves and introduce collective particle–hole pair excitations. These pairs can be approximately described by a bosonic quadratic Hamiltonian. We use Bogoliubov theory to construct a trial state yielding a rigorous Gell-Mann–Brueckner–type upper bound to the ground state energy. Our result justifies the random-phase approximation in the mean-field scaling regime, for repulsive, regular interaction potentials.

Partial coherence and frustration in self-organizing spherical grids - Stella, Federico; Urdapilleta, Eugenio; Luo, Yifan; Treves, Alessandro (Hippocampus)
Nearby grid cells have been observed to express a remarkable degree of long-rangeorder, which is often idealized as extending potentially to infinity. Yet their strict peri-odic firing and ensemble coherence are theoretically possible only in flat environments, much unlike the burrows which rodents usually live in. Are the symmetrical, coherent grid maps inferred in the lab relevant to chart their way in their natural habitat? We consider spheres as simple models of curved environments and waiting for the appropriate experiments to be performed, we use our adaptation model to predict what grid maps would emerge in a network with the same type of recurrent connections, which on the plane produce coherence among the units. We find that on the sphere such connections distort the maps that single grid units would express on their own, and aggregate them into clusters. When remapping to a different spherical environment, units in each cluster maintain only partial coherence, similar to what is observed in disordered materials, such as spin glasses.

Dynamic resource allocation games - Avni, Guy; Henzinger, Thomas A; Kupferman, Orna (Theoretical Computer Science)
In resource allocation games, selfish players share resources that are needed in order to fulfill their objectives. The cost of using a resource depends on the load on it. In the traditional setting, the players make their choices concurrently and in one-shot. That is, a strategy for a player is a subset of the resources. We introduce and study dynamic resource allocation games. In this setting, the game proceeds in phases. In each phase each player chooses one resource. A scheduler dictates the order in which the players proceed in a phase, possibly scheduling several players to proceed concurrently. The game ends when each player has collected a set of resources that fulfills his objective. The cost for each player then depends on this set as well as on the load on the resources in it – we consider both congestion and cost-sharing games. We argue that the dynamic setting is the suitable setting for many applications in practice. We study the stability of dynamic resource allocation games, where the appropriate notion of stability is that of subgame perfect equilibrium, study the inefficiency incurred due to selfish behavior, and also study problems that are particular to the dynamic setting, like constraints on the order in which resources can be chosen or the problem of finding a scheduler that achieves stability.

An efficient projection-type method for monotone variational inequalities in Hilbert spaces - Shehu, Yekini; Li, Xiao-Huan; Dong, Qiao-Li (Numerical Algorithms)
We consider the monotone variational inequality problem in a Hilbert space and describe a projection-type method with inertial terms under the following properties: (a) The method generates a strongly convergent iteration sequence; (b) The method requires, at each iteration, only one projection onto the feasible set and two evaluations of the operator; (c) The method is designed for variational inequality for which the underline operator is monotone and uniformly continuous; (d) The method includes an inertial term. The latter is also shown to speed up the convergence in our numerical results. A comparison with some related methods is given and indicates that the new method is promising.

Strategies to maximize performance in STimulated Emission Depletion (STED) nanoscopy of biological specimens - Jahr, Wiebke; Velicky, Philipp; Danzl, Johann G (Methods)
Super-resolution fluorescence microscopy has become an important catalyst for discovery in the life sciences. In STimulated Emission Depletion (STED) microscopy, a pattern of light drives fluorophores from a signal-emitting on-state to a non-signalling off-state. Only emitters residing in a sub-diffraction volume around an intensity minimum are allowed to fluoresce, rendering them distinguishable from the nearby, but dark fluorophores. STED routinely achieves resolution in the few tens of nanometers range in biological samples and is suitable for live imaging. Here, we review the working principle of STED and provide general guidelines for successful STED imaging. The strive for ever higher resolution comes at the cost of increased light burden. We discuss techniques to reduce light exposure and mitigate its detrimental effects on the specimen. These include specialized illumination strategies as well as protecting fluorophores from photobleaching mediated by high-intensity STED light. This opens up the prospect of volumetric imaging in living cells and tissues with diffraction-unlimited resolution in all three spatial dimensions.

Are two given maps homotopic? An algorithmic viewpoint - Filakovský, Marek; Vokřínek, Lukas (Foundations of Computational Mathematics)
This paper presents two algorithms. The first decides the existence of a pointed homotopy between given simplicial maps 𝑓,𝑔:𝑋→𝑌, and the second computes the group [𝛴𝑋,𝑌]∗ of pointed homotopy classes of maps from a suspension; in both cases, the target Y is assumed simply connected. More generally, these algorithms work relative to 𝐴⊆𝑋.